L'École de Montréal: un quart de siècle de linguistique - Vinay, Jean-Paul (Vingt-cinq ans de linguistique au Canada: hommage à Jean-Paul Vinay, 1979)
Keywords: Linguistique; Université de Montréal

Le dictionnaire de bon langage d'Étienne Blanchard: étude métalexicographique; contribution à l'histoire de la lexicographie québécoise - Prévost, Geneviève (Université Laval, 1996)
Keywords: Linguistique

Choix linguistiques, changements et alternances de langue: les comportements multilingues des italophones de Montréal - Labrie, Normand (Université Laval, 1989)
Keywords: Italiens; Langue

Études de linguistique appliquée sur les structures syntaxiques du français oral de Montréal (Canada) - Dugas, André (Université de Grenoble, 1966)
Keywords: Langue

Participation à la dynamique langagière et appartenance à la communauté linguistique: analyse du français parlé par des francophones et des anglophones de Montréal - Daveluy, Michelle (Université de Montréal, 1994)
Keywords: Langue

La variation entre les formes en ske, kes et kos dans le français parlé à Montréal: étude d'un cas de changement linguistique en cours - Kemp, William (Université du Québec à Montréal, 1979)
Keywords: Langue

Étude lexicale du livre des recettes et dépenses de l'Hôtel-Dieu de Montréal (1696 à 1726) - Francoeur, Sylvie (Université de Montréal, 1993)
Keywords: Communautés religieuses; Hospitalières de Saint-Joseph; Hôpitaux; Hôtel-Dieu; Linguistique

Chronique d'une Académie, 1944-1994: de l'Académie canadienne-française à l'Académie des lettres du Québec - Royer, Jean (L'Hexagone, 1995)
Keywords: Linguistique

La question linguistique à Montréal - Brazeau, Jacques (Revue de l'Institut de sociologie, 1968)
Keywords: Anglophones; Francophones

L’orientation linguistique des allophones à Montréal - Castonguay, Charles (Cahiers québécois de démographie, 1992)
Keywords: Langue

Comportement linguistique des groupes ethniques à Montréal - Ares, Richard (Relations, 1969)
Keywords: Langue

L'évolution de la ségrégation linguistique à Montréal, 1961-1981 - Veltman, Calvin J. (Recherches sociographiques, 1983)
Keywords: Francophones

Intégration linguistique dans les écoles multiethniques de Montréal - Dubois, Jean-François (Université de Montréal, 1991)
Keywords: Langue

Le comportement démographique des groupes linguistiques à Montréal - Termote, Marc (Cahiers québécois de démographie, 1992)
Keywords: Anglophones; Francophones; Fécondité

L'orientation linguistique des mariages mixtes dans la région de Montréal - Castonguay, Charles; Veltman, Calvin (Recherches sociographiques, 1980)
Keywords: Langue; Mariage

La structure résidentielle des transferts linguistiques dans l'agglomération de Montréal - Veltman, Calvin J. (Recherches sociographiques, 1978)
Keywords: Langue

Italianité, conflit linguistique et structure du pouvoir dans la communauté italo-québécoise - Painchaud, Claude; Poulin, Richard (Sociologie et sociétés, 1983)
Keywords: Anglophones; Francophones; Italiens; Langue

Le Débat linguistique au Québec. La communauté italienne et la langue d'enseignement - Taddeo, Donat J.; Taras, Raymond C. (Presses de l'Université de Montréal, 1987)
Keywords: Italiens; Langue

Les Italo-Québécois: acteurs et enjeux des débats politiques et linguistiques au Québec - Linteau, Paul-André (Studi emigrazione/ Études migrations, 1987)
Keywords: Italiens

Les incidences du revenu sur les transferts linguistiques dans la région métropolitaine de Montréal - Veltman, Calvin J. (Recherches sociographiques, 1976)
Keywords: Anglophones; Francophones

Espaces ethniques et question linguistique au Québec: à propos des communautés italienne et portugaise - Da Rosa, Victor M. P.; Poulin, Richard (Canadian Ethnic Studies / Études ethniques au Canada, 1986)
Keywords: Italiens; Portugais

Un an au Québec. La compétence linguistique et l’accès à un premier emploi - Renaud, Jean (Sociologie et sociétés, 1992)
Keywords: Langue; Travail

Tendances de l’assimilation linguistique dans l'ouest de l’île de Montréal et l’ouest de l’Outaouais de 1971 à 1991 - Castonguay, Charles (Cahiers québécois de démographie, 1997)
Keywords: Anglophones; Francophones; Langue

Variabilité linguistique et variabilité sociale dans la communauté francophone de Montréal: présence facultative du de devant l'infinitif dans les constructions avec le verbe être - Lessard, Pierre (Université de Montréal, 1989)
Keywords: Langue

Évolution dans la distribution des revenus de travail des groupes ethniques et linguistiques sur le marché montréalais de 1961 à 1971 - Boulet, Jac-André (Problèmes actuels de l'économie québécoise, 1978)
Keywords: Travail

Jacques Viger - Roy, Camille (Bulletin du parler français au Canada, 1909)
Keywords: Linguistique; Maires; Viger, Jacques

Les aspects démographiques de la question linguistique - Charbonneau, Hubert; Maheu, Robert (Éditeur Officiel du Québec, 1973)
Keywords: Langue

Sociolinguistic Features of Modern Greek as it is Spoken in Montreal - Maniakas, Theodoros (Université McGill, 1983)
Keywords: Grecs; Langue

Les immigrants hispanophones de Montréal et leurs attitudes par rapport aux deux langues officielles - Franco, Barbara (Université du Québec à Montréal, 1995)
Keywords: Espagnols; Langue

La situation sociolinguistique de la communauté marocaine musulmane de Montréal - Boukkouri, Mohammed (Université du Québec à Montréal, 1996)
Keywords: Maghrébins; Marocains; Musulmans

La liaison consonantique en français montréalais - Tousignant, Claude (Université de Montréal, 1978)
Keywords: Francophones; Langue

Left Dislocation in Montreal French - Campion, Elizabeth (University of Pennsylvania, 1984)
Keywords: Langue

A Study of Liaison in Extemporaneous Montreal French Speech - Rosoff, Gary Harry (Columbia University, 1970)
Keywords: Langue

Description phonétique du français de niveau très soigné: (région de Montréal) - Roch, Claude Marie (Université de Montréal, 1975)
Keywords: Langue

Le français populaire de Montréal: description phonologique - Dumas, Denis (Université de Montréal, 1972)
Keywords: Langue

Le bilinguisme chez les jeunes grecs de Montréal - Carroll, Suzanne (Université de Montréal, 1977)
Keywords: Bilinguisme; Grecs

Utilisation des caractéristiques dialectales du français québécois par un groupe d'anglophones bilingues de Montréal - Frigon, Chantal (Université de Montréal, 1997)
Keywords: Langue

Some Linguistic Difficulties of Anglophone Students of Montreal in Learning French - Picard, Léonard (Université de Montréal, 1970)
Keywords: Langue

Linguistic Behaviour and language choice in the Sephardi Community of Montreal - Cale, Béatrice (Université de Montréal, 1989)
Keywords: Juifs; Langue

La chute de la consonne "l" dans les articles définis et les pronoms critiques en français montréalais - Ostiguy, Luc (Université de Montréal, 1979)
Keywords: Langue

Attitudes des Montréalais vis-à-vis des traits phonétiques du français parlé à Montréal: étude sociolinguistique - Lappin, Kerry (Université de Montréal, 1981)
Keywords: Langue

Le franglais de Montréal - Kelley, Lesley Jean (Université de Montréal, 1964)
Keywords: Langue

L'accent en français montréalais - Warren, Ronald (Université de Montréal, 1977)
Keywords: Langue

Context-Determined Variation in Montreal French Vowels - Yaeger, Malcah (University of Pennsylvania, 1979)
Keywords: Francophones; Langue

Étude acoustique des consonnes du français parlé à Montréal: analyse spectrale, intensité, durée - Jacques, Benoît (Université de Montréal, 1983)
Keywords: Langue

Étude de quelques aspects syntaxiques du parler français de Montréal selon le modèle de la grammaire transformationnelle (quantificateurs et négation en français standard et dans le parler de Montréal) - Daoust-Blais, Denise (Université de Montréal, 1970)
Keywords: Langue

Variations morphologiques de l'arménien à Montréal. Aspects sociolinguistiques - Kavassian, Sossy (Université de Montréal, 1981)
Keywords: Arméniens

Analyse fonctionnelle et sociolinguistique de la particule discursive OK en français montréalais - Heisler, Troy (Université Laval, 1996)
Keywords: Francophones

Étude articulatoire des consonnes chez un sujet montréalais - Cardinal, Pierre (Université de Montréal, 1975)
Keywords: Langue

Étude comparative des voyelles nasales du français parisien et du français montréalais - Sanfaçon, Anne (Université de Montréal, 1993)
Keywords: Langue

Le vocabulaire de disponibilité trilingue des jeunes montréalais qui ont l'italien comme langue au foyer - Villata, Bruno (Université Laval, 1985)
Keywords: Italiens; Langue

The English Spoken in Montreal: a Pilot Study - Hamilton, Donald (Université de Montréal, 1958)
Keywords: Langue

Le maintien de la langue d'origine chez des élèves maghrébins à Montréal et la réussite scolaire - Zouali, Ouafaa (Université Laval, 1995)
Keywords: Langue; Maghrébins; Étudiants

Essai de structuration des particularités lexicales du français montréalais - Joseph, Louise (Université de Montréal, 1978)
Keywords: Langue

L'usage et la formation de l'énumération en discours spontané: analyse sociolinguistique du procédé énumératif chez les montréalais francophones - Dubois, Sylvie (Université Laval, 1993)
Keywords: Langue

Analyticity in Montreal Swedish - Gadelii, Karl Erland (Université McGill, 1988)
Keywords: Suédois

Étude de la langue de l'affichage dans la région de Montréal - Labelle, Guy (Université de Montréal, 1970)
Keywords: Enseignes; Langue; Publicité

Réaction dans Le Devoir aux jugements sur la législation linguistique québécoise (1978-1988) - Laporte, Marie-Sylvie (Université de Montréal, 1994)
Keywords: Devoir (Le); Langue

Les interférences anglaises dans le français de Montréal: étude stylistique de la langue de la publicité - Coriat, Annie (Université de Montréal, 1970)
Keywords: Langue; Publicité

L'attitude d'étudiants universitaires anglophones face à diverses variétés de français - Magnon, Céline (Université du Québec à Montréal, 1999)
Keywords: Anglophones; Français; Étudiants

Étude des écarts lexicaux et sémantiques dans les annonces du journal La Minerve (1826-1837) - Tessier, Marie-Claude (Université Laval, 1980)
Keywords: Langue; Minerve (La); Publicité

Un parler parisien - Faribault, Marthe (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)
Keywords: Français; Langue

Montreal's Scottish Community, 1835-65: A Preliminary Study - McNabb, Heather (Université Concordia, 1999)
Keywords: Écossais

The Montreal Loyalists: What Kind of People Were They? - Ruch, John (The Loyalists of Quebec 1774-1825: A Forgotten History, 1989)
Keywords: Loyalistes

Duvernay et la Saint-Jean-Baptiste - Gagner, J.-L. (Chantecler, 1952)
Keywords: Duvernay, Ludger; Société Saint-Jean-Baptiste

The English Speaking Community of Montreal, 1850-1867 - Bawden, James E. A. (Université Wilfrid Laurier, 1975)
Keywords: Anglophones

Le vocabulaire politique et socio-ethnique de Montréal de 1839 à 1842 - Rabotin, Maurice (Didier, 1975)
Keywords: Langue

Langue et société. Le français de Montréal en 1840 - Rabotin, Maurice (Université de Nice, 1972)
Keywords: Langue

Irish Radicalism and the Roman Catholic Church in Quebec and Ireland, 1833-1834: O'Callaghan and O'Connell Compared - Slattery, Maureen (Canadian Catholic Historical Association, Historical Studies, 1997)
Keywords: Irlandais; O'Callaghan, Edmund B.; Rébellions; Églises

Les étrangers sous le Régime français - Grenier, Hélène (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)

The Irish in the Province of Canada in the Decade Leading to Confederation - Lyne, Daniel Colman (Université McGill, 1960)
Keywords: Irlandais

Une quête identitaire entre mythe et histoire: les Juifs ashkénazes à l'aventure de l'Amérique en Québec - Barriault, Lise (Université du Québec à Montréal, 1998)
Keywords: Juifs

Tradition and Social Change: An Ideological Analysis of the Montreal Jewish Immigrant Ghetto in the Early Twentieth Century - Oiwa, Keinosuke (Cornell University, 1988)
Keywords: Juifs

The Saint Patrick's Society of Montreal: Ethno-Religious Realignment in a Nineteenth-Century National Society - James, Kevin (Université McGill, 1997)
Keywords: Irlandais

The Changing Influence of French on Montreal English: A Case Study of Prestige Differential - Harris, Brigitte (Université Concordia, 1986)
Keywords: Bureau des écoles protestantes; Langue

The Antiochan Orthodox Syrians of Montreal 1905-1980: an Historical Study of Cultural and Social Change Over Three Generations - Marino, Norman (Université Concordia, 1994)
Keywords: Syriens

Strategies of Survival Among Illegal Migrants in Montreal - Raposo, Cremilde (Université Concordia, 1996)
Keywords: Travail

Safeguarding Mother Tamil in Multicultural Quebec: Sri Lankan Legends, Canadian Myths, and the Politics of Culture - Brunger, Fern (Université McGill, 1994)
Keywords: Sri Lankais

Renegotiating Home and Identity: Experiences of Gujarati Immigrant Women in Suburban Montreal - Nair, Roopa (Université McGill, 1998)
Keywords: Femmes; Indiens

Pressure Group Politics: Case Study of the St. Leonard Schools Crisis - Parisella, John E. (Université McGill, 1971)
Keywords: Italiens; Saint-Léonard (crise de)

Pour un patrimoine pluriethnique - Blanc, Bernadette (Continuité, 1998)
Keywords: Côte-des-Neiges; Patrimoine; Quartiers

L'évolution spatiale des groupes ethniques à Montréal, 1871-1981 - McNicoll, Claire (École des hautes études en sciences sociales, 1986)
Keywords: Mobilité résidentielle

L’identité ethnique chez les jeunes Montréalais d’origine immigrée - Meintel, Deirdre (Sociologie et sociétés, 1992)
Keywords: Chiliens; Grecs; Portugais; Salvadoriens

Les jeunes de la deuxième génération haïtienne au Québec: entre la communauté « réelle » et la communauté « représentée » - Potvin, Maryse (Sociologie et sociétés, 1997)
Keywords: Haïtiens

Education and Integration of Immigrant Minorities: A Case Study of the Haitian Community in Quebec - Pompilus, Léopold (Université Concordia, 1999)
Keywords: Haïtiens

Double majorité et multiciplicité ethnoculturelle à Montréal - Anctil, Pierre (Recherches sociographiques, 1984)
Keywords: Anglophones; Francophones; Langue

Un nouveau cadre méthodologique pour l'étude de la ségrégation résidentielle appliqué à Montréal (1931-71) - Langlois, André (The Canadian Geographer / Le Géographe canadien, 1985)

The Kosher Meat War and the Jewish Community Council of Montreal, 1922-1925 - Robinson, Ira (Canadian Ethnic Studies / Études ethniques au Canada, 1990)
Keywords: Alimentation; Cohen, Hirsch; Juifs; Rosenberg, Yudel

Ethnic Strategies in the Urban Economy - Olson, Sherry (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Keywords: Travail

Modes d'acculturation et d'identité située: Le cas des immigrants haïtiens de Montréal - Clément, Richard; Sylvestre, André; Noels, Kimberly (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Keywords: Haïtiens

A Study of the Changes in the Distribution and Mobility of Armenians in the Montreal Region, 1972-1979 - Chichekian, Garo (Cahiers de géographie du Québec, 1981)
Keywords: Arméniens; Mobilité résidentielle

Les Français à Montréal - Grosmaire, Jean-Louis (Cahiers de géographie du Québec, 1983)
Keywords: Français

Les organisations féminines de la communauté juive montréalaise, 1918-1948 - Filotas, Sarah (Université de Montréal, 1998)
Keywords: Femmes; Juifs

Changement dans l'identité culturelle des immigrants à Montréal et facteurs qui influencent ce changement - Barrios, Pablo Gomez (Université du Québec à Montréal, 1989)
Keywords: Colombiens

Le mouvement ouvrier juif au Canada (1904-1920) - Belkin, Simon (Septentrion, 1999)
Keywords: Congrès juif canadien; Juifs; Poalei Zion (Mouvement sioniste ouvrier)

Coping with Racism: the Chinese Experience in Canada - Helly, Denise; Chan, Kwok Bun (Canadian Ethnic Studies / Études ethniques au Canada, 1987)
Keywords: Chinois

Problèmes de communication interculturelle et ruptures des cadres chez des immigrants et immigrantes latino-américains à Montréal - Hudon, Nathalie (Université du Québec à Montréal, 1994)
Keywords: Latino-Américains

Les modalités d'insertion des chiliennes à Montréal une décade d'immigration - Ramirez-Cassali, Lucy (Université du Québec à Montréal, 1986)
Keywords: Chiliens

A Foothold in the Whirlpool: Canada's Iberian Refugee Movement - Reed, Patrick (Université Concordia, 1996)
Keywords: Juifs

Enjeux et contraintes de la communication interculturelle au Québec: perceptions et réactions de la communauté juive montréalaise au théâtre de Michel Tremblay - Bonjour, Nathalie (Université du Québec à Montréal, 1993)
Keywords: Juifs; Théâtre; Tremblay, Michel

L'identité transnationale et l'installation des Chinois du Vietnâm à Montréal - LaRochelle, Jean (Université de Montréal, 1999)
Keywords: Chinois

The Italians of Quebec - Linteau, Paul-André (Boundaries of Identity: A Quebec Reader, 1992)
Keywords: Italiens

Des Italo-Belges au Canada: résultats d'une première enquête - Morelli, Anne (Les immigrants préférés: Les Belges, 1999)
Keywords: Belges; Italiens

Moroccan Jews and their Adaptation to Montreal Life - Cohen, Yolande; Lévy, Joseph J. (Renewing our Days: Montreal Jews in the Twentieth Century, 1995)
Keywords: Juifs; Maghrébins; Marocains

101 du français, il en faut plus, pas moins - Société Saint-Jean-Bapiste de Montréal (L'Action nationale, 1993)
Keywords: Francophones

Historiography, Myth and Group Relations: Jewish and Non-Jewish Québécois on Jews and New France - Menkis, Richard (Canadian Ethnic Studies / Études ethniques au Canada, 1991)
Keywords: Histoire; Juifs

La famille juive à Montréal au tournant du XXe siècle - Soucy, Isabelle (Université du Québec à Montréal, 1999)
Keywords: Famille; Juifs

Les Franco-Américains à Montréal au début du XXe siècle - Rodrigue, Martine (Université du Québec à Montréal, 1997)
Keywords: Américains; Francophones

L'identité des immigrants latino-américains à Montréal - Thomas, Ève (Université de Montréal, 1998)
Keywords: Latino-Américains

Élites et organisation communautaire chez les juifs marocains à Montréal - Cohen, Yolande; Lévy, Joseph (Annuaire de l'Émigration, 1995)
Keywords: Juifs; Maghrébins; Marocains

Blacks in Québec Society, Past and Present - La Grenade-Meunier, Monique; Fehmiu Brown, Paul (Ministère des Affaires internationales, de l'Immigration et des Communautés culturelles et ministère de l'Éducation, 1995)
Keywords: Noirs

La présence des Noirs dans la société québécoise d'hier et d'aujourd'hui - La Grenade-Meunier, Monique; Fehmiu Brown, Paul (Ministère des Affaires internationales, de l'Immigration et des Communautés culturelles et ministère de l'Éducation, 1995)
Keywords: Noirs

Les facteurs de maintien de l'identité collective arménienne chez les jeunes adultes de la diaspora montréalaise - Lenoir-Achdjian, Annick (Université de Montréal, 1996)
Keywords: Arméniens

Réflexions sur les pratiques communicationnelles des institutions de la société d'accueil dans l'insertion des immigrantes et des immigrants au Québec: 1986-1996 - Fournel, Claude-Jean (Université du Québec à Montréal, 1999)

Tur Malka: flâneries sur les cimes de l'histoire juive montréalaise - Anctil, Pierre (Septentrion, 1997)
Keywords: Juifs

Étude descriptive du phénomène d'intégration de la communauté libanaise à la société québécoise à Montréal - Chamoun, Myrna (Université du Québec à Montréal, 1998)
Keywords: Libanais

Les voyelles orales dans le français parlé à Montréal - Santerre, Laurent (Université des sciences humaines de Strasbourg, 1971)
Keywords: Langue

L'immigration française au Canada de 1945 à 1960 - Leblond, Francis (Université Laval, 1993)
Keywords: Français

Montréal, les Juifs et l'école - Corcos, Arlette (Septentrion, 1997)
Keywords: Juifs

Les immigrants préférés: Les Belges - Jaumain, Serge (Presses de l'Université d'Ottawa, 1999)
Keywords: Belges

Les relations interethniques et interraciales de parents haïtiens et de leurs enfants dans deux quartiers multiethniques de Montréal - Brodrique, Lise (Université du Québec à Montréal, 1992)
Keywords: Haïtiens; Quartiers

Les représentations sociales de la violence chez des adolescents et des adolescentes d'origines ethniques différentes de Montréal - Gobeil, André (Université Laval, 1993)
Keywords: Délinquance

La mobilité résidentielle intra-urbaine des Portugais de première génération à Montréal - Teixeira, José Carlos (Université du Québec à Montréal, 1986)
Keywords: Mobilité résidentielle; Portugais

Nature et corrélats des orientations d'acculturation chez des Antillais à Montréal - Moïse, Léna Céline (Université du Québec à Montréal, 1997)
Keywords: Caribéens

Le Montréal juif d'autrefois / Monṭreol fun nekhṭen - Medresh, Israël (Septentrion, 1997)
Keywords: Juifs

English Caribbean Immigrant Entrepreneurs in Montreal - Hall, Margaret-Ann (Université Concordia, 1999)
Keywords: Anglophones; Caribéens

L'immigré salvadorien à Montréal: interprétation d'un processus d'intégration - Ruano, Mauricio (Université du Québec à Montréal, 1997)
Keywords: Salvadoriens

"Des Québécois importés et leurs niches": l'immigration et l'expression de l'ethnicité dans les pratiques économiques des Portugais indépendants du Québec - Fonséca, Félix (Université Laval, 1999)
Keywords: Portugais

Politiques d'intégration et résistances ethniques au Québec: le cas d'immigrants libanais depuis 1975 - Abou-Hsab, Gaby (Université du Québec à Montréal, 1996)
Keywords: Libanais

Montréal dans le réseau international des villes francophones - Breton, Roland J.-L. (Montréal: tableaux d'un espace en transformation, 1992)

La Communauté grecque du Québec - Ioannou, Tina (Institut québécois de recherche sur la culture, 1983)
Keywords: Grecs

Folktales and Social Structure: the Case of the Chinese in Montreal - Hoe, Ban Seng (Canadian Folklore Canadien, 1979)
Keywords: Chinois

Les Chinois à Montréal, 1877-1951 - Helly, Denise (Institut québécois de recherche sur la culture, 1987)
Keywords: Chinois

The Jew in Canada - Hart, Arthur D. (s.é., 1926)
Keywords: Juifs

Montreal's King of Italian Labour: A Case Study of Padronism - Harney, Robert F. (Labour / Le travailleur, 1979)
Keywords: Cordasco, Antonio; Italiens

Zloty Jubileusz Parafii Swietej Trojcy W Montrealu, Que., 1916-1966 - Waruszynski, Zbigniew (Glos Polski, 1967)
Keywords: Polonais

Évolution de la localisation résidentielle des principaux groupes ethniques immigrants, Montréal, 1971-1981 - Veltman, Calvin J.; Polese, Mario; Leblanc, Marc (INRS-Urbanisation, 1986)
Keywords: Logement; Mobilité résidentielle

Clarence de Sola and Early Zionism in Canada, 1898-1920 - Tulchinsky, Gerald (The Jews of North America, 1987)
Keywords: De Sola, Clarence; Juifs; Sionisme

Gli Italiani in Canada - Vangelisti, Guglielmo F. S. (Chiesa Italiana di N. S. Della Difesa, 1955)
Keywords: Italiens

Bases économiques et structure sociale, 1931-1971 - Szacka, Alexandra (Juifs et réalités juives au Québec, 1984)
Keywords: Juifs

La situation des immigrants à Montréal: étude sur l'adaptation occupationnelle, les conditions résidentielles et les relations sociales (Conseil des oeuvres de Montréal, 1959)

Population Characteristics (Distribution by Age and Sex) of the Jewish Community of Montreal - Rosenberg, Louis (Canadian Jewish Congress, 1955)
Keywords: Juifs

Changes in the Jewish Population in the Old Area of Jewish Settlement in Montreal Within a Radius of One Mile from Corner of Jeanne Mance St. and Villeneuve ave, in the Period from 1951 to 1957 - Rosenberg, Louis (Canadian Jewish Congress, 1958)
Keywords: Juifs

The British Immigrant: His Social and Economic Adjustment in Canada - Reynolds, Lloyd G. (Oxford University Press, 1935)
Keywords: Britanniques

The Italians of Montreal: From Sojourning to Settlement, 1900-1921 - Ramirez, Bruno; Del Balso, Michael (Les Editions du Courant, 1980)
Keywords: Italiens

The Italians of Montreal: From Sojourning to Settlement, 1900-1921 - Ramirez, Bruno; Del Balso, Michael (Little Italies in North America, 1981)
Keywords: Italiens

La recherche sur les Italiens du Québec - Ramirez, Bruno (Questions de culture, 1982)
Keywords: Italiens

The Social Construction of Ethnicity: the Case of English Montrealers - Price, Kenneth Arthur (Université York, 1980)
Keywords: Anglophones

Ethnicity on Trial: The Italians of Montreal and the Second World War - Ramirez, Bruno (On Guard for Thee: War, Ethnicity, and the Canadian State, 1939-1945, 1988)
Keywords: Guerre; Italiens

La géographie résidentielle des immigrants et des groupes ethniques: Montréal, 1971 - Polese, Mario; Hamel, Charles; Bailly, Antoine (INRS-Urbanisation, 1978)

Points de vue sur la communauté juive de Montréal (Mordecai Richler) - Perrotin, Françoise (Le facteur religieux dans la vie publique canadienne, 1980)
Keywords: Juifs; Richler, Mordecai

Les Italiens au Québec - Painchaud, Claude; Poulin, Richard (Asticou / Critiques, 1988)
Keywords: Italiens

The Structure of Dispersal: The Japanese Canadian Community of Montreal, 1942-52 - Oiwa, Keibo (Canadian Ethnic Studies / Études ethniques au Canada, 1986)
Keywords: Japonais

Réhabilitation historique - Morin, Victor (Les Cahiers des Dix, 1958)
Keywords: Société Saint-Jean-Baptiste

Das Deutschtum in Montreal - Mollmann, Albert Von (Fisher, 1937)
Keywords: Allemands

Official Opening, Samuel Bronfman House. Commemorating Fifty Years of Service by the Canadian Jewish Congress, Montreal, May 24, 1970 (s.é., 1970)
Keywords: Congrès juif canadien; Juifs

Gli Italiani di Montreal : Note e Profili - Mingarelli, Giosafat (Jos) (Centro Italiano Attivita Commerciali-Artistiche, 1980)
Keywords: Italiens

Gli Italiani di Montreal. Note e Profili - Mingarelli, Giosafat (Jos) (Centro Italiano Attivita Commerciali-Artistiche, 1967)
Keywords: Italiens

Les relations entre les groupes ethniques à Montréal: zones de conflit et zones d'échange - Mailhiot, Bernard (Éducation des adultes, 1961)

La montée du cosmopolitisme montréalais - Linteau, Paul-André (Questions de culture, 1982)

The Italians of Quebec: Key Participants in Contemporary Linguistic and Political Debates - Linteau, Paul-André (Arrangiarsi. The Italian Immigration Experience in Canada, 1989)
Keywords: Italiens

The Reconquest of Montreal. Language Policy and Social Change in a Bilingual City - Levine, Marc V. (Temple University Press, 1990)
Keywords: Anglophones; Francophones

Les Ethniques et la ville. L'aventure urbaine des immigrants portugais à Montréal - Lavigne, Gilles (Editions du Préambule, 1987)
Keywords: Portugais

Une étude des statistiques des mariages inter-ethniques à Montréal pour les années 1951 et 1962 - Lacoste, Yvon (Université de Montréal, 1966)
Keywords: Mariage

Une diaspora francophone au Québec. Les Juifs sépharades - Lasry, Jean-Claude (Questions de culture, 1982)
Keywords: Juifs

Aspects de géographie sociale de la population polonaise de Montréal - Laberge, L. (Université Laval, 1972)
Keywords: Polonais

The Ukrainian Community in Montreal - Kelebay, Yarema Gregory (Université Concordia, 1975)
Keywords: Ukrainiens

Les Italiens de Montréal: l'adaptation dans une société pluraliste - Boissevain, Jeremy (Information Canada, 1971)
Keywords: Italiens

The Italians of Montreal: Social Adjustment in a Plural Society - Boissevain, Jeremy (Arno Press, 1975)
Keywords: Italiens

The Italians of Montreal: Social Adjustment in a Plural Society - Boissevain, Jeremy (Information Canada, 1971)
Keywords: Italiens

Intégration des Juifs marocains au Canada. Monographie de la communauté juive marocaine à Montréal - Benaim, Esther (Université de Paris III, 1974)
Keywords: Juifs; Maghrébins; Marocains

Juifs et réalités juives au Québec - Anctil, Pierre; Caldwell, Gary (Institut québécois de recherche sur la culture, 1984)
Keywords: Juifs

The Immigrant Experience: Personal Recollections of Jewish Garment Workers in Canada, 1900-1930 - Berson, Seemah Cathline (Université de Colombie-Britannique, 1980)
Keywords: Confection; Juifs

Le rendez-vous manqué: les Juifs de Montréal face au Québec de l'entre-deux-guerres - Anctil, Pierre (Institut québécois de recherche sur la culture, 1988)
Keywords: Juifs

Langues parlées par les néo-Québécois à Montréal - Ares, Richard (Relations, 1969)
Keywords: Langue

Les Portugais du Québec: éléments d'analyse socio-culturelle - Alpalhao, Joao Antonio; Da Rosa, Victor Manuel Pereira (Editions de l'Université d'Ottawa, 1979)
Keywords: Portugais

A Minority in a Changing Society: the Portuguese Communities of Quebec - Alpalhao, Joao Antonio; Da Rosa, Victor Manuel Pereira (University of Ottawa Press, 1980)
Keywords: Portugais

The Portuguese in a changing society - Alpalhao, J. Antonio; Da Rosa, Victor M. P. (Two Nations, Many Cultures, 1983)
Keywords: Portugais

Urban Villagers: The Greek Community in Montreal - Gavaki, Efie (Two Nations, Many Cultures, 1983)
Keywords: Grecs

Italiani in Canada: il caso di Montreal - Farnocchia, F. (Bolletino della Societa Geographica Italiana, 1981)
Keywords: Italiens

La contribution des Français de Montréal à la vie économique - Dhavernas, Marc (Almanach du Courrier français. La présence française, 1983)
Keywords: Français

The Irish in Montreal, 1867-1896 - Cross, D. Suzanne (Université McGill, 1969)
Keywords: Irlandais

Les Grecs du Québec: analyse historique et sociologique - Constantinides, Stephanos (O Metoikos-Le Métèque, 1983)
Keywords: Grecs

Les Haïtiens au Québec - Dejean, Paul (Presses de l'Université du Québec, 1978)
Keywords: Haïtiens

The Slovakian Community in Montreal - Brown, Wilfrid Harold (Université McGill, 1927)
Keywords: Slovaques

Dynamique ethnique et évolution socio-politique du Québec: le cas de la population grecque de Montréal - Bredimas-Assimopoulos, Nadia (Sociologie et sociétés, 1983)
Keywords: Grecs

The Occupational Adjustments of Montreal Negroes, 1941-1948 - Potter, Harold Herbert (Université McGill, 1949)
Keywords: Noirs

The Development and Social Adjustment of the Jewish Community in Montreal - Seidel, Judith (Université McGill, 1939)
Keywords: Juifs

The Montreal Negro Community - Israel, Wilfrid Emerson (Université McGill, 1928)
Keywords: Noirs

The Social Structure of the Italian and Ukrainian Communities in Montreal, 1935-1937 - Bayley, Charles M. (Université McGill, 1939)
Keywords: Italiens; Ukrainiens

Our Distant Brethren: Alexander Harkavy on Montreal Jews - 1888 - Sarna, Jonathan D. (Canadian Jewish Historical Society Journal / Société de l'histoire juive canadienne, 1983)
Keywords: Harkavy, Alexander; Juifs

La communauté sépharade de Montréal: une analyse ethno-historique des structures communautaires - Filion, Fernand-G. (Université Laval, 1979)
Keywords: Juifs

Histoire des paroisses polonaises à Montréal - Dolmat, Wacław Bazyli (Université de Montréal (texte en polonais), 1952)
Keywords: Polonais

La formation d'un quartier ethnique: les Portugais de Montréal - Lavigne, Gilles (Université de Montréal, 1979)
Keywords: Portugais

Transplantation humaine : une enquête sociologique sur une agglomération polono-ukrainienne dans un secteur de la ville de Montréal en 1947-1948 - Coté, Alphonse (Université de Montréal, 1948)
Keywords: Polonais; Ukrainiens

The Egyptians in Montreal: A New Color in the Canadian Ethnic Mosaïc - Wassef, Nadia Hanna (Université McGill, 1978)
Keywords: Égyptiens

The Occupational Adjustment of the British Immigrant in Montreal - Reynolds, Lloyd George (Université McGill, 1933)
Keywords: Britanniques

The Social Adjustment of Hungarian Refugees in Montréal - Gellert, Judith (Université McGill, 1964)
Keywords: Hongrois

French and English in the Economic Structure of Montreal - Hughes, Everett C.; Mcdonald, Margaret L. (Revue canadienne d'économique et de science politique / Canadian Journal of Economics and Political Science, 1941)
Keywords: Anglophones; Francophones

Structure démographique et distribution spatiale de la population Haïtienne à Montréal 1971-1982 - Bastien, André (Université de Montréal, 1984)
Keywords: Haïtiens

Les étudiants africains à Montréal: aliénation - Djitai, Mahaman; Ekpe, Christopher P.; Mvilongo-Tsala, Anselme (Université de Montréal, 1974)
Keywords: Africains; Étudiants

L'attitude d'adolescents d'origine grecque à Montréal à l'égard de leur langue maternelle - Margellou, Anthi (Université de Montréal, 1988)
Keywords: Grecs; Langue

Rupture et continuité chez des familles québécoises francophones de Montréal: étude ethnologique des rapports entre parents âgés et enfants - Bédard, Jean-Luc (Université de Montréal, 1992)
Keywords: Famille

Conflit entre les Néo-Canadiens et les francophones de Montréal - Cappon, Paul (Université de Paris, 1971)
Keywords: Anglophones; Bilinguisme; Francophones

Des participes passés en français parlé à Montréal - Ouellet, Martine (Université de Montréal, 1986)
Keywords: Langue

Adaptation de l'enfant haïtien à Montréal: étude réalisée auprès de 27 familles haïtiennes à Montréal - Chrispin Brutus, Merlaine (Université de Montréal, 1970)
Keywords: Enfants; Famille; Haïtiens

L'identité ethnoculturelle chez des jeunes d'origine vietnamienne à Montréal - Méthot, Caroline (Université de Montréal, 1993)
Keywords: Vietnamiens

Parcours d'un marqueur sociolinguistique: les pronoms non-clitiques du pluriel en français parlé de Montréal - Blondeau, Hélène (Université de Montréal, 1999)
Keywords: Langue

L'usage des déterminants démonstratifs dans la communauté francophone de Montréal en 1971 et en 1984 - Daveluy, Michelle (Université de Montréal, 1987)
Keywords: Langue

The Attitudes of Students of Greek Origin in a French-Language Learning Situation in a Québec Secondary School - Waite, Richard (Université McGill, 1991)
Keywords: Grecs; Langue; Étudiants

The Ethnolinguistic Reality of Montreal Greeks - Maniakas, Theodoros (Université de Montréal, 1990)
Keywords: Grecs

La transmission d'une mémoire sociale à travers quatre générations: le cas des Juifs ashkénazes à Montréal - Olazabal, J.-Ignace (Université de Montréal, 1999)
Keywords: Juifs

Proposition d'un cadre de recherche opérationnelle pour l'étude de la ségrégation résidentielle ethnique dans la région métropolitaine de Montréal - Bérubé, Sylvain (Université de Montréal, 1994)

Estudio de la comunidad etnocultural gallega de Montreal - Rubio-Ardanaz, Juan Antonio (Université de Montréal, 1987)
Keywords: Espagnols

Acculturation and Consumption Behaviour of Italian-Canadians in Montreal - Reedijk, Robert (Université Concordia, 1991)
Keywords: Italiens

Culture vinique et pathologies éthyliques chez les italiens de Montréal: étude exploratoire - Cardinal, Nicole (Université de Montréal, 1984)
Keywords: Italiens

Étude de la structure de la phrase: élaboration de techniques et comparaison d'enfants de milieu défavorisé et de milieu moyen - Pagé, Michel (Université de Montréal, 1971)
Keywords: Enfants; Langue

Identité ethnique et acculturation chez des étudiants juifs sépharades à Montréal - Brami, Paula (Université de Montréal, 1996)
Keywords: Juifs; Étudiants

Les couples mixtes africains/haïtiens et québécoises: une étude exploratoire - Passerieux, Catherine (Université du Québec à Montréal, 1989)
Keywords: Africains; Haïtiens

Représentations sociales de la culture des jeunes de la communauté haïtienne de Montréal et construction de leur identité - Valéry, Joseph Olivier (Université de Montréal, 1997)
Keywords: Haïtiens

Modes d'acculturation, stress acculturatif et race: le cas des jeunes étudiants haïtiens de la première et de la seconde générations de Montréal - Sylvestre, André (Université de Montréal, 1992)
Keywords: Haïtiens; Étudiants

Connaissances et habitudes alimentaires des familles immigrantes portugaises - Vidigal Aragao, Ana Maria (Université de Montréal, 1979)
Keywords: Alimentation; Portugais

L'analyse factorielle à trois entrées: une application à l'espace ethnique montréalais - Langlois, André (Université Laval, 1982)

Acculturation et identité ethnique d'un groupe d'Égyptiens à Montréal - Collin, Louise (Université de Montréal, 1981)
Keywords: Égyptiens

Adaptation and Integration Process of some African Ismaili Youths of Second-Generation in Montreal - Jinah, Parvin (Université de Montréal, 1996)
Keywords: Africains

Étude de la variation des pronoms sujets définis et indéfinis dans le français parlé à Montréal - Laberge, Suzanne (Université de Montréal, 1977)
Keywords: Langue

Culture Change and the Redefinition of Ethnicity: the Case of Portuguese Youth in Montréal - Claudio, Fernanda (Université de Montréal, 1990)
Keywords: Portugais

Nourriture et culture: étude des pratiques alimentaires des Chinois de Montréal - Bélanger, Danielle (Université de Montréal, 1991)
Keywords: Alimentation; Chinois

Ethnicité et idéologie: le cas des italophones de Montréal - Oriolo, Stefano (Université Laval, 1990)
Keywords: Italiens

Ethnicity as a Symbol System: a Theoretical Discussion Exemplified by Case Studies of Spaniards in Montreal - Fernandez, Ronald Louis (Université McGill, 1972)
Keywords: Espagnols

Les voyelles nasales du français canadien, région de Montréal: étude de phonétique expérimentale - Charbonneau, René (Université de Strasbourg, 1965)
Keywords: Langue

La peur de l'étranger: les Chinois à Montréal de 1885 à 1947 - Harel, Nathalie (Université de Montréal, 1995)
Keywords: Chinois

Influence de l'acculturation sur l'alimentation des haïtiennes de Montréal - Petit, Éva (Université de Montréal, 1996)
Keywords: Alimentation; Haïtiens

Équivalence et grammaticalisation - Thibault, Pierrette (Université de Montréal, 1983)
Keywords: Langue

A. M. Klein and Mordecai Richler: Canadian Responses to the Holocaust - Brenner, Rachel Feldhay (Journal of Canadian Studies / Revue d'études canadiennes, 1989)
Keywords: Juifs; Klein, A. M.; Richler, Mordecai

Montreal's Italians and the Socio-Economy of Settlement, 1900-1930: Some Historical Hypotheses - Ramirez, Bruno (Urban History Review / Revue d'histoire urbaine, 1981)
Keywords: Italiens

Distribution spatiale et structure démographique: la population haïtienne à Montréal, 1971-1982 - Bastien, André (Centre de recherches caraïbes de l'Université de Montréal, 1985)
Keywords: Haïtiens

You are in Montreal Now: Zvi Hirsch Masliansky on Montreal Jews - 1888 - Zola, Garry P. (Canadian Jewish Historical Society Journal / Société de l'histoire juive canadienne, 1985)
Keywords: Cohen, Hirsch; Juifs

The Third Solitude: A. M. Klein's Jewish Montreal, 1910-1950 - Tulchinsky, Gerald (Journal of Canadian Studies / Revue d'études canadiennes, 1984)
Keywords: Juifs; Klein, A. M.

From Heterogeneity to Consensus: The Jewish Community of Montreal - Bauer, Julien (Canadian Jewish Society, 1980)
Keywords: Juifs

Langage et ethnicité: communication interculturelle à Montréal, 1977-1991 - Moise, Lena C.; Bourhis, Richard Y. (Canadian Ethnic Studies / Études ethniques au Canada, 1994)
Keywords: Langue

A Profile of the Successful Greek Immigrant Student in Montreal - Bombas, Leonidas C. (Université Concordia, 1981)

Languages in Contact: Error Analysis of Italian Childrens' Compositions in a Multilingual Context - Samperi Mangan, Jacqueline (Université McGill, 1991)
Keywords: Enfants; Italiens; Langue

La population juive de Montréal est-elle victime d'une ségrégation qu'elle se serait elle-même imposée? - Légaré, Jacques (Recherches sociographiques, 1965)
Keywords: Juifs

Langue et identité chez les Québécois d’ascendance italienne - Fortier, Anne-Marie (Sociologie et sociétés, 1992)
Keywords: Italiens; Langue

Intra-Ethnic Differences of the Perceptions of Aged Italian Women in Receiving Care - Bonar, Rita Aguzzi (Université McGill, 1993)
Keywords: Femmes; Italiens

Hometown and Family Ties: The Lebanese-Syrians of Montreal, 1905-1950 - Moser, Diane (Université McGill, 1990)
Keywords: Libanais; Syriens

Intégration civique sans acculturation. Les Grecs à Montréal - Bredimas-Assimopoulos, Nadia (Sociologie et sociétés, 1975)
Keywords: Grecs

Évolution de la répartition spatiale des groupes ethniques dans l'espace résidentiel montréalais, 1931-1971 - Langlois, André (Cahiers de géographie du Québec, 1985)
Keywords: Logement; Mobilité résidentielle

Les visages du Plateau Mont-Royal - LaFerrière, Suzanne (Continuité, 1995)
Keywords: Plateau Mont-Royal; Quartiers

Montreal of Yesterday - Medres, Israel I. (The Eagle Publishing Co., 1947)
Keywords: Juifs

L'unilinguisme français et le projet souverainiste du Parti québécois vus par la communauté juive du Québec (1974-1981) - Cloutier, Caroline (Bulletin d'histoire politique, 1999)
Keywords: Juifs; Langue; Nationalisme; Partis politiques

Understanding the Patterns of Language Use of Chinese Children in a Montreal Community School - Curdt-Christiansen, Xiao Lan (Université McGill, 1999)
Keywords: Chinois; Langue; Étudiants

The Role of The Gazette in Linguistic Group Relations in Quebec: A Contextual Approach - Ruvinsky, Ilene G. (Université McGill, 1984)
Keywords: Anglophones; Francophones; Montreal Gazette

The Language Problem and School Board Reform on the Island of Montréal - Mackay, Murdo (Université McGill, 1987)
Keywords: Langue

The Greek Day School Socrates in Montreal: Its Development and Impact on Student Identity, Adjustment and Achievement - Bombas, Leonidas C. (Université McGill, 1988)
Keywords: Grecs

The Genesis Period of the Jewish People's School in Montreal - August, David (Université Concordia, 1975)
Keywords: Juifs

The Education of Italians in Montreal, 1895 to 1960 - Gadler, Yves Carmelo Luciano (Université McGill, 1994)
Keywords: Italiens

School Climates: a Comparative Exploratory Case Study between Jewish Day Schools and Public Schools in Western Montreal - Weinberg, Sara (Université Concordia, 1979)
Keywords: Juifs

L'insegnamento dell'italiano a Montreal verso il Duemila. Insegnamento e apprendimento al livello post-secondario in un contesto plurilingue - Picciano, Giovanna A. (Université McGill, 1997)
Keywords: Italiens; Langue

L’ethnicisation de l’établissement humain en Amérique du Nord: l’exemple du quartier portugais à Montréal - Lavigne, Gilles; Daudelin, Nanouk; Ritchot, Gilles (Cahiers de géographie du Québec, 1995)
Keywords: Portugais; Quartiers

Les quartiers multiethniques montréalais: une lecture urbaine - Germain, Annick (Recherches sociographiques, 1999)
Keywords: Quartiers

Les Canadiens français vus par les consuls de France à Québec et à Montréal de 1859 à 1900 - Savard, Pierre (Revue d'histoire de l'Amérique française, 1967)

L’entrepreneurship ethnique à Montréal: première esquisse - Juteau, Danielle; Daviau-Guay, Jocelyne; Moallem, Minoo (Cahiers québécois de démographie, 1992)

L'attitude des chinois de Montréal vis-à-vis des stratégies ethniques des banques - Hakimian, Edith (École des hautes études commerciales de Montréal, 1994)
Keywords: Banques; Chinois

Rapports familiaux chez les Italiens du Québec - Ramirez, Bruno (Critère, 1982)
Keywords: Famille; Italiens

Aspects de la thématique juive dans le Canadian Jewish News, édition de Montréal, 1977-1982 - Anctil, Pierre (Canadian Ethnic Studies / Études ethniques au Canada, 1984)
Keywords: Canadian Jewish News; Juifs

The Montreal Irish and the Great War - Burns, Robin S. (Canadian Catholic Historical Association, Study Sessions, 1985)
Keywords: Guerre; Irlandais

Pour en finir avec un mythe: le refus des écoles catholiques d'accepter les immigrants - Gagnon, Robert (Bulletin d'histoire politique, 1997)
Keywords: Commission des écoles catholiques de Montréal

La construction sociale des relations interethniques et interraciales chez des jeunes vietnamiens et asiatiques du sud-est d'une école secondaire de Montréal - Filion, Gilbert (Université du Québec à Montréal, 1991)
Keywords: Vietnamiens

L'international, un devoir au quotidien depuis 1910 - Char, Antoine (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le)

Étude exploratoire sur l'adaptation socio-sexuelle des immigrants latino-américains gais à Montréal - Pérez Luis, Javier Éric (Université du Québec à Montréal, 1997)
Keywords: Latino-Américains

An Exploratory Study of a Group of Montréal Anglophone Teachers' Attitudes toward Multicultural Education - Ganji, Mahnaz (Université du Québec à Montréal, 1998)
Keywords: Anglophones; Enseignants

La Grande Paix de Montréal de 1701: les voies de la diplomatie franco-amérindienne - Havard, Gilles (Recherches amérindiennes au Québec, 1992)
Keywords: Autochtones; Français; Grande Paix de Montréal

La mise en place des paysages ethniques, 1871-1971 - McNicoll, Claire (Montréal 2001. Visages et défis d'une métropole, 1998)

Espaces ethniques en devenir: une enquête géographique sur les Haïtiens et les Vietnamiens de Montréal - Guillemette-Roc, Diane (Université du Québec à Montréal, 1986)
Keywords: Haïtiens; Vietnamiens

Les scénarios sexuels des jeunes adultes latino-américains de Montréal l'impact de l'acculturation et du genre - Arroyo, Javiera (Université du Québec à Montréal, 1997)
Keywords: Latino-Américains

Les quartiers multiethniques montréalais, lieux de sociabilité publique - Germain, Annick (Barcelona-Montréal: desarrollo urbano comparado / développement urbain comparé, 1998)
Keywords: Quartiers

L'implantation de la Maison de la culture haïtiano-québécoise - Preval, Guerdy Jacques (Université du Québec à Montréal, 1987)
Keywords: Haïtiens

Une époque fertile en miracles - Fournier, Marcel; Rodriguez, Véronique (Montréal métropole, 1880-1930, 1998)

La communauté libanaise à Montréal: essai de géographie culturelle - Lami, Nathalie (Université du Québec à Montréal, 1992)
Keywords: Libanais

Les associations vietnamiennes à Montréal - Dorais, Louis-Jacques (Canadian Ethnic Studies / Études ethniques au Canada, 1992)
Keywords: Vietnamiens

Community Associations and their Relations with the State. The Case of the Arab Associative Network of Montréal - Aboud, Brian (Université du Québec à Montréal, 1991)
Keywords: Arabes

Les associations vietnamiennes à Montréal et l'adaptation des réfugiés - Dorais, Louis-Jacques (Université Laval, 1990)
Keywords: Vietnamiens

Alphabétisation en créole à Montréal - Dugazon, Marc-Arthur (Université du Québec à Montréal, 1987)
Keywords: Créoles; Haïtiens

Étude comparative des valeurs (rokeach) des groupes de jeunes d'origine québécoise, haïtienne et vietnamienne d'une école secondaire publique de Montréal - Chirca, Natalia (Université du Québec à Montréal, 1990)
Keywords: Haïtiens; Vietnamiens; Étudiants

Les organisations de solidarité avec le Chili à Montréal, 1973-1993 - Hervas Segovia, Epiganio Roberto (Université du Québec à Montréal, 1997)
Keywords: Chiliens

Anomie et délinquance chez un groupe d'adolescents anglais de la région métropolitaine de Montréal - Rivest, Jean (Université du Québec à Montréal, 1994)
Keywords: Anglophones; Délinquance

Bagarres entre militaires et "zoot-suiters" survenues à Montréal et à Verdun en juin 1944: problème de langue, de relations entre civils et militraires ou de rébellion juvénile? - Durflinger, Serge Marc (L'impact de la Deuxième Guerre mondiale sur les sociétés canadienne et québécoise, 1998)
Keywords: Armée; Vêtements

Usages familiaux des médias en situation de transition: le cas de sept Roumains à Montréal - Theodorescu, Christiana-Nicola (Université du Québec à Montréal, 1995)
Keywords: Roumains

Le contrôle social et la construction de l'Autre: la police dans un quartier multiethnique - Symons, Gladys L.; Loiselle, Marie-Josée (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Police; Quartiers

Influence du processus d'insertion sur l'identité des femmes libanaises nouvellement arrivées à Montréal - Cossette, Maryse (Université du Québec à Montréal, 1998)
Keywords: Femmes; Libanais

Les représentations d'adolescents d'origine haïtienne (14 ans et plus) de la région de Montréal de leur intégration sociale à l'école secondaire et de leur identité culturelle - Valcin, Paul-Bermude (Université du Québec à Montréal, 1996)
Keywords: Haïtiens

Immigration et communautés ethno-culturelles - Taschereau, Sylvie (Guide d'histoire du Québec: du régime français à nos jours: bibliographie commentée, 1991)

Les représentations sociales des minorités ethniques dans la presse francophone montréalaise en 1989 - Rivière, Anne (Université du Québec à Montréal, 1992)

Immigrant Perceptions of Canadian schools: a Study of Greek Parents in Montréal - Shore, Bettina (Université McGill, 1979)
Keywords: Grecs

Les radios communautaires et leurs publics CIBL face à l'indifférence de l'auditoire d'origine africaine - Belibi Mengueme, Mireille Simone (Université du Québec à Montréal, 1998)
Keywords: Africains; Radio

A Statistical Study of the Number and Percentage of Jewish Children in the Protestant Schools of Greater Montreal and the Suburb of Greater St. Martin (Chomedy) in the Period from 1878 to 1968 - Rosenberg, Louis (Canadian Jewish Congress, 1969)
Keywords: Bureau des écoles protestantes; Juifs

Jewish Children in the Protestant Schools of Greater Montreal in the Period from 1878 to 1962 - Rosenberg, Louis (Canadian Jewish Congress, 1962)
Keywords: Bureau des écoles protestantes; Juifs; Protestants

The Education of Black Students in Montreal Schools: an Emerging Anglophone Problem, a Non-Existent Francophone Preoccupation - Laferriere, Michel (Ethnic Canadians: Culture and Education, 1978)
Keywords: Noirs; Étudiants

The Montreal Chinese Hospital 1918-1982: A Case Study of an Ethnic Institution - Ho, Kwong-Ming (Université McGill, 1984)
Keywords: Chinois; Hôpital chinois; Hôpitaux

The Political Consequences of the Jewish School Question, Montreal, 1925-1933 - Rome, David (Société de l'histoire juive canadienne / Jewish Historical Society of Canada, 1977)
Keywords: Juifs

Le vocabulaire de deux générations de Québécois: différences temporelles (1966 et 1981) et régionales (Montréal et Québec) - Jobin, Jean-Louis (Centre international de recherche sur le bilinguisme / International Center for Research on Bilingualism, 1987)
Keywords: Bourassa, Samuel; Langue; Photographie

The Role of the Black Community in Educating Blacks in Montreal, from 1910 to 1940, with Special Reference to Reverend Dr Charles Humphrey Este - Bertley, June A (Université McGill, 1982)
Keywords: Este, Charles Humphrey; Noirs

Swiss National Society, 1874-1974 - Schweizer, Leo (The Society, 1974)
Keywords: Suisses; Swiss National Society

Immigration et démographie - Szacka, Alexandra (Juifs et réalités juives au Québec, 1984)
Keywords: Juifs

Jewish Intermarriage in Montreal, 1962-1972 - Lasry, Jean-Claude; Bloomfield-Schachter, E. (Jewish Sociology Studies, 1975)
Keywords: Juifs; Mariage

The Universal Negro Improvement Association of Montreal, 1917-1979 - Bertley, Leo W. (Université Concordia, 1980)
Keywords: Noirs; Universal Negro Improvement Association of Montreal

The Commission des écoles catholiques de Montréal and the Neo-Canadian Question: 1947-63 - Behiels, Michael D. (Canadian Ethnic Studies / Études ethniques au Canada, 1986)
Keywords: Commission des écoles catholiques de Montréal

The French and English Social Elites in Montreal - Ross, Eileen (Université McGill, 1941)
Keywords: Anglophones; Francophones

The Irish Migration to Montreal, 1847-1867 - Keep, George Rex (Université McGill, 1948)
Keywords: Irlandais

Who Shall Separate Us?: The Montreal Irish and the Great War - Burns, Robin S. (The Untold Story: The Irish in Canada, 1988)
Keywords: Guerre; Irlandais

The Loyalists and the Arts in Montreal - Ruch, John (The Loyalists of Quebec 1774-1825: A Forgotten History, 1989)
Keywords: Loyalistes

Quand la société Saint-Jean-Baptiste a-t-elle été fondée? - Rumilly, Robert (Revue d'histoire de l'Amérique française, 1947)
Keywords: Duvernay, Ludger; Société Saint-Jean-Baptiste

Conflit de culture et criminalité des Italiens à Montréal - Ribordy, François Xavier (Université de Montréal, 1970)
Keywords: Criminalité; Italiens

Ukrainian Bilingual Education in the Montreal Public School System, 1911-1945 - Melnyk, Iryna (Université McGill, 1987)
Keywords: Ukrainiens

Le SIDA et la discrimination envers la population noire de Montréal - Gélineau, Lucie (Université de Montréal, 1988)
Keywords: Noirs

La signification des soins reliés à la grossesse et à l'accouchement de couples iraniens à Montréal - Gharehbagh, Zahra A. (Université de Montréal, 1997)
Keywords: Iraniens

Montréal, les Juifs et l'école - Siboni Corcos, Arlette (Université de Montréal, 1993)
Keywords: Juifs

La participation des lituaniens aux associations volontaires: une étude du degré de participation aux associations volontaires intra et extra ethniques de 127 Lituaniens gradués de l'école du samedi à Montréal - Lukosevicius, Irena K. (Université de Montréal, 1971)
Keywords: Lituaniens

Representing Twentieth Century Canadian colonial Identity: the Imperial Order Daughters of the Empire (IODE) - Pickles, Catherine Gillian (Université McGill, 1996)
Keywords: Britanniques; Femmes

L'intervention de réadaptation auprès des adolescents haïtiens: problèmes rencontrés, compréhension du phénomène et pistes d'intervention - Mercier, Chantale (Université du Québec à Trois-Rivières, 1998)
Keywords: Haïtiens

Les minorités ethniques et les décisions des juges du Tribunal de la jeunesse de Montréal - Faille, Michèle (Université de Montréal, 1991)
Keywords: Délinquance; Juges; Tribunaux

Les perceptions des groupes ethno-culturels face aux programmes communautaires du S.P.C.U.M. - Théagène, Jean-Manassé (Université de Montréal, 1993)
Keywords: Communauté urbaine

Étude de l'appartenance au groupe "Québécois" à partir des images et des identités véhiculées par la presse communautaire à Montréal - Contandriopoulos, Damien (Université de Montréal, 1997)
Keywords: Journalistes

Études slaves au Canada et particulièrement au centre d'études slaves à l'Université de Montréal et à l'Institut est et sud européen et à l'Université d'Ottawa - Nowaczek, Jozef (Université de Montréal, 1951)
Keywords: Ukrainiens; Université de Montréal

Étude sur la réceptivité des étudiants canadiens-français de l'Université de Montréal à l'égard des étudiants immigrés - Grandbois, Jean-Marie (Université de Montréal, 1953)
Keywords: Francophones; Université de Montréal; Étudiants

Interkulturelle Landeskunde im Bereich des Deutschen als Fremdsprache an kanadischen Hochschulen: Dokumentation einer Fallstudie am Department of German Studies der McGill University, Montreal, Quebec, Kanada - Mollinger, Karin (Université McGill, 1996)
Keywords: Allemands; Université McGill

Situation résultant de la présence des Néo-québécois dans huit écoles françaises de la C.E.C.M. - Primeau, Jacques (Université de Montréal, 1977)
Keywords: Commission des écoles catholiques de Montréal

L'enseignement de la prononciation du français dans les écoles secondaires anglaises de Montréal - Bazzit, Naïma (Université de Montréal, 1988)
Keywords: Langue

Itinéraires scolaires et socialisation ethnique: le cas de deux écoles judéo-québécoises - Prentice, Mark (Université Laval, 1990)
Keywords: Juifs

Étude des caractéristiques de la douance chez des sujets issus de la minorité culturelle haïtienne à Montréal - Dikamba, Kamvidie Marguerite (Université de Montréal, 1986)
Keywords: Enfants; Haïtiens

A Study of the Effects of Acculturation on Sex-Role Attitudes of Chinese Couples, and the Subsequent Impact of these Sex-Role Attitudes on Couple's Household Task Sharing & Decision Making - Hayes, Janet (Université Concordia, 1995)
Keywords: Chinois; Femmes

Le français radiophonique à Montréal - Brunel, Gilles (Université de Montréal, 1970)
Keywords: Langue; Radio

Program Planning in English as a Second Language at the Protestant School Board of Greater Montreal: A Historical Study - Slobod, Shirley (Université Concordia, 1982)
Keywords: Bureau des écoles protestantes; Langue

An Age Rich in Miracles - Fournier, Marcel; Rodriguez, Véronique (Montreal Metropolis, 1880-1930, 1998)

Presse ethnique et socialisation politique: le cas de la communauté chinoise de Montréal - Jolicœur, Martin (Université Laval, 1995)
Keywords: Chinois

La scolarité à l'étranger: cas des élèves marocains au Collège Français (Montréal) - Aherdane, Mohamed (Université de Montréal, 1983)
Keywords: Maghrébins; Marocains; Étudiants

Invasion, Succession and Conflict: The Case of St. Leonard, Quebec - Smith, Courtney David Campbell (Pennsylvania State University, 1974)
Keywords: Francophones; Italiens; Saint-Léonard; Saint-Léonard (crise de)

La société québécoise et sa langue jugée par cinq écrivains de "Parti pris" - Arguin, Maurice (Université Laval, 1970)
Keywords: Girouard, Laurent; Godin, Gérald; Jasmin, Claude; Major, André; Parti Pris; Renaud, Jacques; Écrivains

Les Amérindiens sous le Régime français - Lachance, André; Savoie, Sylvie (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)
Keywords: Autochtones

The Irish Adjustment in Montreal - Keep, George Rex (Canadian Historical Review, 1950)
Keywords: Irlandais

The Creative Yiddish Press - From Exciting Vitality to Slow Death - Levendel, Lewis (A Century of Canadian Jewish Press, 1880s-1980s, 1989)
Keywords: Juifs

Seven Decades of Chronicling the Community - The Canadian Jewish Chronicle of Montreal and Toronto - Levendel, Lewis (A Century of Canadian Jewish Press, 1880s-1980s, 1989)
Keywords: Canadian Jewish Chronicle; Juifs

An Everyday Miracle: Yiddish Culture in Montreal - Robinson, Ira; Anctil, Pierre; Butovsky, Mervin (Véhicule Press, 1990)
Keywords: Juifs

Social Aspirations - The Canadian Jewish Review of Toronto and Montreal - Levendel, Lewis (A Century of Canadian Jewish Press, 1880s-1980s, 1989)
Keywords: Juifs

Constructing Italian Ethnicity: A Comparative Study of Two Italian Language Newspapers in Australia and Canada, 1947-1957 - Iuliano, Susanna (Université McGill, 1994)
Keywords: Italiens

Chinese-Canadian Women in Montreal: Case Studies in the Importance of Education - Li, Sharon (Université McGill, 1995)
Keywords: Chinois; Femmes

Imagining Ethnicity. The Role of the Montreal Bangladeshi Press in Ethnic Cohesion - Ahmed, Shameem (Université McGill, 1997)
Keywords: Bengalis

Montréal. Une société multiculturelle - McNicoll, Claire (Histoire et société. Modernités, 1993)
Keywords: Mobilité résidentielle

La solidarité entre générations: Haïtiennes âgées à Montréal - Haldemann, Varena (Sociologie et sociétés, 1995)
Keywords: Femmes; Haïtiens

La présence haïtienne à Montréal: évolution démographique et spatiale - Bastien, André (Cahiers québécois de démographie, 1986)
Keywords: Haïtiens

La concentration ethnique dans les écoles de langue française de l’île de Montréal: un portrait statistique - Mc Andrew, Mary; Ledoux, Michel (Cahiers québécois de démographie, 1995)
Keywords: Francophones; Langue

Gender, Race, and Power: the Chinese in Canada, 1920-1950 - Huang, Belinda (Université McGill, 1998)
Keywords: Chinois

The French Canadians under the Royal Institution for the Advancement of Learning, 1818-1829 - Boulianne, Réal G. (Université d'Ottawa, 1964)
Keywords: Royal Institution for the Advancement of Learning

La perception de la qualité de la langue au Québec de 1960 à 1992 d'après les opinions publiées dans La Presse - Lajeunesse, Lyse (Université de Sherbrooke, 1997)
Keywords: Langue; Presse (La)

Sophie Speaks Out - Suburban Weekly Fills the Montreal Void - Levendel, Lewis (A Century of Canadian Jewish Press, 1880s-1980s, 1989)
Keywords: Juifs

Quelques problèmes politiques et sociaux (1933-1935) d’après L’Action nationale, Le Canada et Le Devoir - Dupont, Antonin (Université de Montréal, 1965)
Keywords: Action nationale (L'); Canada (Le); Devoir (Le)

L'Action française de Montréal, 1917-1928: étude suivie d'un index - Jolicœur, Louis-Philippe (Université de Montréal, 1959)
Keywords: Action française (L')

Almanach du Courrier français: la présence française - Pleau, Marcel (Union nationale française, 1983)
Keywords: Français

Ukrainian Community Life in Montreal: Social Planning Implications - Tokar, Ann M. (Université McGill, 1992)
Keywords: Ukrainiens

The Young Men's Hebrew Association of Montreal: A Study of the Role of the Formal and Informal in an Ethnic Institution - Solomon, David N. (Université McGill, 1942)
Keywords: Juifs

The Ideological and Intellectual Baggage of Three Fragments of Ukrainian Immigrants: a Contribution to the History of the Ukrainians in Quebec (1910-1960) - Kelebay, Yarema Gregory (Université Concordia, 1992)
Keywords: Idéologies; Ukrainiens

Dispersal and Concentration of the Vietnamese Canadians: A Montreal Case Study - Lavoie, Caroline (Université McGill, 1988)
Keywords: Vietnamiens

Armenian Immigrants in Canada and their Distribution in Montreal - Chichekian, Garo (Cahiers de géographie du Québec, 1977)
Keywords: Arméniens

L'idée du refus comme mémoire et comme identité chez les artisans visuels contemporains québécois - Carani, Marie (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)
Keywords: Borduas, Paul-Émile; Peinture

Destination: Montréal: l'étude de l'émigration en provenance de Casacalenda (Molise, Italie) - Malpas, Nicole (Cahiers québécois de démographie, 1997)
Keywords: Italiens

Borduas revu à travers la figure de Claude Gauvreau - Fisette, Jean (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)
Keywords: Automatistes; Borduas, Paul-Émile

Le fascisme et les Italiens à Montréal: une histoire orale, 1922-1945 - Salvatore, Filippo (Guernica, 1995)
Keywords: Idéologies; Italiens

Expulsion des immigrants indésirables à Montréal: 1911-1914 - Legeay, Guilaine (Université d'Angers, 1999)

Les zones résidentielles des Indochinois à Montréal - Lavoie, Caroline (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Quartiers

Les Libanais d'immigration récente: insertion ou exclusion? - Fortin, Sylvie (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Libanais; Quartiers

La polysensorialité dans les discours symboliques plastiques québécois (1930-1960) - Lupien, Jocelyne (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)

Représentation de l'espace urbain et laïcisation de la pratique - Trépanier, Esther (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)

Ethnicité, culture et société globale: le discours de leaders d'origine haïtienne, italienne, juive et libanaise de la région de Montréal - Therrien, Marthe (Université du Québec à Montréal, 1993)
Keywords: Haïtiens; Italiens; Juifs; Libanais

Community and Identity in Nineteenth Century Montreal: The Founding of Saint Patrick's Church - Leitch, Gillian I. (Université d'Ottawa, 1999)
Keywords: Irlandais; St. Patrick (église); Églises

Les relations interculturelles entre les immigrants d'origine sénégalaise et la population d'accueil québécoise: jalons d'une analyse des systèmes de représentation et des stratégies d'intégration - Ndoye, Amadou (Université Laval, 1999)
Keywords: Sénégalais

Afro-Canadian Activism in the 1960s - Stamadianos, Peter (Université Concordia, 1994)
Afro-Canadian activism became increasingly militant in the 1960s. The rise in militancy in the Afro-American leadership of the 1960s was one factor contributing to the new era of black politics in Canada. Increased immigration from the West Indies also encouraged the proliferation of Afro-Canadian organizations dedicated to challenging racial discrimination. Afro-Canadian activism, however, developed in a substantially different manner than black politics in the United States. On the whole, most Afro-Canadian organizations and leaders were considerably less militant in their tactics and strategies than their counterparts in the United States. Internecine divisions over ancestral origin were also more pronounced in Canada where the black population was ethnically heterogeneous when compared to the Afro-American community.
Keywords: Africains; Noirs

L'immigration belge au Canada: une histoire en devenir - Jaumain, Serge; Sanfilippo, Matteo (Les immigrants préférés: Les Belges, 1999)
Keywords: Belges

Fascism and the Italians of Montreal: an Oral History, 1922-1945 - Salvatore, Filippo (Guernica, 1998)
Keywords: Idéologies; Italiens

The History of the Federation of Jewish Philanthropies of Montreal - Zeith, Mordecai E. (Yeshiva University, 1974)
Keywords: Federation of Jewish Philanthropies; Juifs; Philanthropie

Peintres juifs et modernité / Jewish Painters and Modernity: Montréal 1930-1945 - Trépanier, Esther (Centre Saidye-Bronfman, 1987)
Keywords: Juifs; Peinture

Italian Art and Artists in Nineteenth-Century Quebec: A Few Preliminary Observations - Lacroix, Laurier (Arrangiarsi. The Italian Immigration Experience in Canada, 1989)
Keywords: Italiens; Peinture; Sculpture

Three Sectors of Ukrainian Community in Montreal, 1899-1970: An Intellectual Gestalt Approach - Kelebay, Yarema Gregory (Y. G. Kelebay, 1980)
Keywords: Ukrainiens

Antécédents idéologiques de la communauté ashkénaze québécoise - Szacka, Alexandra (Juifs et réalités juives au Québec, 1984)
Keywords: Idéologies; Juifs

Synagogues, Jewish Schools and Other Jewish Community Facilities as Affected by the Migration of the Jewish Population in Metropolitan Montreal, 1951-1956 - Rosenberg, Louis (Canadian Jewish Congress, 1956)
Keywords: Juifs; Églises

Processus migratoire, communauté et bourgeoisie italo-québécoise - Painchaud, Claude (Université du Québec à Montréal, 1982)
Keywords: Italiens

Les anglophones de Montréal; émigration et évolution des attitudes 1978-1983 - Locher, Uli (Publications du Québec, 1988)
Keywords: Anglophones

A Study of the Cultural and Language Problems of Greek Immigrant Children in Montreal - Lewis, Eileen Mary (Université Bishop, 1973)
Keywords: Enfants; Grecs

Les Communautés culturelles du Québec originaires de l'Europe centrale et de l'Europe du Sud - Lefebvre, Michel; Oryschuk, Yuri (Fides, 1985)
Keywords: Allemands; Autrichiens; Croates; Espagnols; Français; Grecs; Italiens; Portugais; Serbes; Slovènes; Suisses

Three Fragments of the Ukrainian Community in Montreal, 1899-1970: a Hartzian Approach - Kelebay, Yarema Gregory (Ukrainian Review, 1981)
Keywords: Ukrainiens

The Intellectual Baggage of Three Waves of Ukrainian Immigrants to Montreal - Kelebay, Yarema Gregory (New Soil - Old Roots: The Ukrainian Experience in Canada, 1983)
Keywords: Ukrainiens

Three Fragments of the Ukrainian Community in Montreal, 1899-1970: A Hartzian Approach - Kelebay, Yarema Gregory (Canadian Ethnic Studies / Études ethniques au Canada, 1980)
Keywords: Ukrainiens

La contribution des Québécois des groupes ethniques autres que français et britannique au développement du Québec - Malservisi, Mauro F. (Éditeur Officiel du Québec, 1973)

The Social Adjustment of British Immigrant Families in Verdun and Pointe-Saint-Charles - Davidson, Mary (Université McGill, 1933)
Keywords: Britanniques; Pointe-Saint-Charles; Quartiers; Verdun

Juifs marocains à Montréal: témoignages d'une immigration moderne - Berdugo-Cohen, Marie; Cohen, Yolande; Lévy, Joseph (VLB, 1987)
Keywords: Juifs; Maghrébins; Marocains

Italian Immigrant Women in Post-War Montreal - Atri, Josephine (Université Concordia, 1980)
Keywords: Femmes; Italiens

Les Juifs progressistes au Québec - Gottheil, Allen (Editions par ailleurs, 1988)
Keywords: Amram, Maurice; Bennett, Arnold; Bernheim, J. C.; Cherniak, Donna; Gray, Stan; Juifs; Levy, Andrea; Mergler, Donna; Morgentaler, Henry; Neamtan, Nancy; Roback, Léa

Occupational Mobility and Achievements of Post-War Chinese Immigrants in Montreal - Chiang, Frances Shiu-Ching (Université McGill, 1978)
Keywords: Chinois; Travail

Diverging Identities: The Presbyterian Metis of St. Gabriel Street, Montreal - Brown, Jennifer (The New Peoples: Being and Becoming Metis in North America, 1985)
Keywords: Famille; Métis; Presbytériens; Protestants; St Gabriel Street Presbyterian Church

A New Immigration to Canada: North African Jews in Montreal - Elbaz, André (Journal of Canadian Studies / Revue d'études canadiennes, 1968)
Keywords: Juifs; Maghrébins

A Jewish Communal Welfare Institution in a Changing Society - Tzuk, Yogev (Université Concordia, 1981)
Keywords: Baron de Hirsch Institute; Juifs

L'idéologie nationaliste de la Société Saint-Jean Baptiste de Montréal - Blain, Jean-Pierre (Université de Montréal, 1964)
Keywords: Idéologies; Nationalisme; Société Saint-Jean-Baptiste

The Attitudes of the Montreal Jewish Community toward French Nationalism and Separatism - Coleman, Romalis (Université McGill, 1967)
Keywords: Francophones; Juifs; Nationalisme

The Economic and Social Adjustment of Slavic Immigrants in Canada with Special Reference to the Ukrainian of Montreal - Mamchur, Stephen (Université McGill, 1935)
Keywords: Ukrainiens

Les réfugiés chiliens à Montréal, niveaux d'intégration et de rupture - Grmela, Sonia (Université de Montréal, 1989)
Keywords: Chiliens

L'expérience vécue par des jeunes maghrébins dans des centres de réadaptation à Montréal - Jouiet, Rabina (Université de Montréal, 1999)
Keywords: Maghrébins

Sujets et identités multiples: analyse des histoires de vie d'un groupe d'immigrants italiens à Montréal - Peressini, Mauro (Université de Montréal, 1991)
Keywords: Italiens

A Logic of Ethnicity: A Study of the Significance and Classification of Ethnic Identity among Montréal Portuguese - Fernandez, Ronald (Université McGill, 1977)
Keywords: Portugais

Les Libanais d'immigration récente à Montréal: insertion ou exclusion - Fortin, Sylvie (Université de Montréal, 1995)
Keywords: Libanais

The Process of Integration of Immigrants: the Case of Italians in Montreal - Duce, Graciela E. (Université de Montréal, 1977)
Keywords: Italiens

The Japanese in Montreal: Socio-Economic Integration and Ethnic Identification of an Immigrant Group - Keiko, Minai (Université McGill, 1977)
Keywords: Japonais

Exile, Transnational Connections, and the Construction of Identity: Tibetan Immigrants in Montreal - Gardner, Jane (Université Concordia, 1999)
Keywords: Tibétains

Le travail d'établissement des réfugiés salvadoriens à Montréal - Beausoleil, Julie (Université de Montréal, 1998)
Keywords: Salvadoriens

Effects of Migration on Alcohol Use: A Survey of Drinking Patterns, Attitudes and Alcohol-Related Problems among Ecuadorians in Ecuador and in Montreal - Vega Mansilla, Gustavo (Université McGill, 1982)
Keywords: Alcool; Équatoriens

Adaptation post-migratoire des couples marocains à Montréal: satisfaction maritale et stress psychologique - El Haïli, Saïda (Université de Montréal, 1998)
Keywords: Maghrébins; Marocains

Immigration, acculturation et santé mentale: les Libanais à Montréal - Sayegh, Liliane (Université de Montréal, 1992)
Keywords: Libanais

Montreal Anglophones: Social Distance and Emigration - Lange, Mélanie (Université McGill, 1985)
Keywords: Anglophones

Le processus de migration, la mobilité sociale et l'acculturation chez les ressortissants d'origine portugaise à Montréal - Romao, Isabel (Université de Montréal, 1972)
Keywords: Portugais

Vietnamese-Chinese Refugees in Montreal - Lam, Lawrence (Université York, 1983)
Keywords: Chinois; Vietnamiens

Immigration et adaptation des haïtiens à Montréal - Marchand, Ronald (Université de Montréal, 1981)
Keywords: Haïtiens

Les activités économiques des immigrantes portugaises au Portugal et à Montréal à travers les récits de vie - Januário, Ilda (Université de Montréal, 1988)
Keywords: Femmes; Portugais; Travail

Accessibility to Municipal Services for Ethnocultural Populations in Toronto and Montreal - Tate, Ellen (Université Laval, 1992)

Independent Jewish Societies of Montreal. A Survey of the Nature and Extent of Philanthropic Programmes - 1949 - Shriar, Rupert (Université McGill, 1953)
Keywords: Juifs; Philanthropie

Identity, Place and Community: A Latin American Locale in Montreal - Occhipinti, Joseph (Université McGill, 1996)
Keywords: Latino-Américains

The Social Integration and Adjustment of Post-War Immigrants in Montreal and Toronto - Ossenberg, R. J. (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1964)
Keywords: Anglophones; Francophones

L'affaire du château Maisonneuve - Angers, François-Albert (L'Action nationale, 1979)
Keywords: Hôtellerie; Reine-Élizabeth (hôtel)

An Inquiry into the Socio-Cultural Factors Affecting the Education of Women in Northern Nigeria: A Case Study of Northern Nigerian Women in Montreal - Badejo, Oluyemisi (Université Concordia, 1981)
Keywords: Femmes; Nigériens; Étudiants

Kateri Tekakwitha - Jodoin, Rachel (Célébrités canadiennes, 1983)
Keywords: Autochtones; Iroquois

When Nationalisms Collide: Montreal's Italian Community and the St. Léonard Crisis, 1967-1969 - D'Andrea, Giuliano E. (Université McGill, 1989)
Keywords: Italiens; Saint-Léonard (crise de)

TEKAKWITHA (Tekaouïta, Tagaskouïta, Tegakwitha), Kateri - Béchard, Henri (Dictionnaire biographique du Canada, 1966)

The Role of the Greek Orthodox Church in the Greek Community of Montreal - Katma, Fotini (Université Concordia, 1986)
Keywords: Grecs; Églises

Locating Crisis Representations of Race and Space in the English media, Montreal, 1987-1992 - Hadlaw, Janin (Université Concordia, 1996)
Keywords: Montreal Gazette; Noirs; Police; Télévision

Les communautés ethniques et rituelles dans le diocèse de Montréal - Paquette, Mario (L'Église de Montréal, aperçus d'hier et d'aujourd'hui, 1836-1986, 1986)

Die Geschichte des deutschsprachigen Theaters in Montreal von seinen Anfängen 1953 bis 1997 - Kremer, Johanna (Université McGill, 1998)
Keywords: Allemands; Théâtre

Religion and Refugee Adaptation: the Vietnamese in Montreal - Dorais, Louis-Jacques (Canadian Ethnic Studies / Études ethniques au Canada, 1989)
Keywords: Vietnamiens

Étudier la pluriethnicité à l'ère de la mondialisation - Meintel, Deirdre; Piché, Victor; Fortin, Sylvie (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité - Meintel, Deirdre; Piché, Victor; Juteau, Danielle; Fortin, Sylvie (L'Harmattan, 1997)
Keywords: Côte-des-Neiges; Quartiers

Rapports sociaux-ethniques à Côte-des-Neiges, un quartier de Montréal - Simon-Barouh, Ida (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Montréal en Amérique du Nord - Mercer, John (Montréal: tableaux d'un espace en transformation, 1992)

Femmes immigrantes et sida: les Haïtiennes de Montréal - Landry, Gervaise Patricia (Université Laval, 1994)
Keywords: Femmes; Haïtiens

Les Juifs Sépharades à Montréal: traces passagères et marqueurs spatiaux d'une minorité dans une métropole nord-américaine - Brière, Céline (Université d'Angers, 1990)
Keywords: Juifs; Métropole

Le rôle des femmes dans deux nouvelles religions à Montréal: l'Association pour la conscience de Krishna (A.I.C.K.) et le Mouvement néo-sannyasin de Rajneesh - Laissy, Noelle (Université du Québec à Montréal, 1988)
Keywords: Femmes

Le théâtre yiddish à Montréal / Yiddish Theatre in Montreal - Larrue, Jean-Marc (Jeu, 1996)
Keywords: Juifs; Théâtre

Catholicisme romain ou catholicisme culturel? À propos de la messe et d'autres pratiques rituelles chez les francophones du Grand Montréal - Turcotte, Paul-André (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)

Le quartier Côte-des-Neiges: fiction statistique ou milieu d'insertion pour les groupes d'immigrants? - Piché, Victor; Bélanger, Liane (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1997)
Keywords: Côte-des-Neiges; Quartiers

The Kahnawake Iroquois and the Lower-Canadian Rebellions, 1837-1838 - Sossoyan, Matthieu (Université McGill, 1999)
Keywords: Autochtones; Iroquois; Rébellions

Governing Montreal: The Impact of French-English Differences on Metropolitan Politics - Sancton, Andrew (Université d'Oxford, 1979)
Keywords: Anglophones; Francophones

Governing the Island of Montreal: Language Differences and Metropolitan Politics - Sancton, Andrew (University of California Press, 1985)
Keywords: Anglophones; Francophones

The French-Speaking Theatre of Montreal, 1937-1963 - Rickett, Olla (Cornell University, 1964)
Keywords: Théâtre

Les communautés "protestantes" francophones de Montréal: esquisse d'une réalité - Raguy, Dominique (Le facteur religieux dans la vie publique canadienne, 1980)
Keywords: Francophones; Protestants

Montreal's Oldest Black Congregation: Union Church, 3007 Delisle Street - Bertley, Leo W. (Bilongo Publishers, 1976)
Keywords: Noirs; Union Church; Églises

Magyar Reformatus Egyhaz: Hungarian United Church, Montreal, Quebec - Benyak, Irma; Komjathy, Aladar (Hungarian United Church, 1976)
Keywords: Hongrois; Hungarian United Church; Églises

L'Église catholique et la communauté italienne de Montréal - Énard, Anne-Marie (Le facteur religieux dans la vie publique canadienne, 1980)
Keywords: Italiens

Femme et judaïsme. Les femmes immigrantes sépharades à Montréal - Dinelle, Johanne; Barette-Dalphond, Andrée (Université du Québec à Montréal, 1985)
Keywords: Femmes; Juifs

Residential Persistence in an Ethnic Working-Class Community: St. Ann's Ward, Montreal, 1871 to 1891 - Solonysznyj, Peter (Université Concordia, 1988)
Keywords: Quartiers; Sainte-Anne

La musique populaire haïtienne à Montréal - Juste-Constant, Voegeli (Université de Montréal, 1985)
Keywords: Haïtiens; Musique

Port du voile et profils d'appartenance chez des adolescentes musulmanes à Montréal - Machouf, Anousheh (Université de Montréal, 1991)
Keywords: Musulmans

Cultures en fragments: l'ethnicité et la religion chez les migrants indo-trinidadiens de Montréal - Beauchemin, Robert (Université de Montréal, 1995)
Keywords: Indiens

La mission catholique chinoise dans le cadre du "Chinatown" montréalais: étude socio-historique - Crépeau, Hélène (Université de Montréal, 1950)
Keywords: Chinois; Missions

Life in an Urban Chassidic Community: Insulation and Proselytization. - Shaffir, William (Université McGill, 1972)
Keywords: Juifs

Le concept de la sécurité nationale et les atteintes aux droits de la personne: les Italiens du Québec entre 1939 et 1945 - Le Comte, Marie (Université de Montréal, 1982)
Keywords: Italiens; Prisons

French and English in the Institutional Structure of Montreal: a Study for the Social and Economic Division of Labour - Jamieson, Stuart Marshall (Université McGill, 1938)
Keywords: Anglophones; Francophones

Influence of the Jewish Dietary Laws (Kashruth) on the Food Habits and Nutritional Intakes of Observant Jews in Montreal - Shatenstein, Bryna (Université de Montréal, 1992)
Keywords: Alimentation; Juifs

Collaboration inter-organisationnelle dans un contexte ethnique à Montréal - Kimonyo, Jean-Paul (Université de Montréal, 1995)

La congrégation franco-protestante: étude exploratoire de l'organisation d'une congrégation protestante de langue française à Montréal - Le Cavalier, Guy (Université de Montréal, 1964)
Keywords: Francophones; Protestants

Les églises ukrainiennes à Montréal - Hrymak-Wynnycky, Nadia A. (Université de Montréal, 1964)
Keywords: Ukrainiens; Églises

The Pre-Baptism Instruction of Italian Immigrants at Our Lady of Pompei Parish in Montreal - Fugolo, Joseph (Université de Montréal, 1980)
Keywords: Italiens

The Montreal Chassidic Community: Community Boundaries and the Maintenance of Ethnic Identity - Shaffir, William (Université McGill, 1969)
Keywords: Juifs

Life in a Religious Community: the Lubavitcher Chassidim in Montreal - Shaffir, William (Holt, Rinehart & Winston, 1974)
Keywords: Juifs

La catéchèse à la Mission portugaise de Montréal - Bruno, Maria José (Université de Montréal, 1990)
Keywords: Missions; Portugais

Développement d'un modèle d'évangélisation au sein d'une communauté haïtienne à Montréal-Nord - Mensah, Jean-Roger (Université de Montréal, 1982)
Keywords: Haïtiens

Residential Patterns of New Immigrants and Linguistic Integration - Montgomery, Catherine; Renaud, Jean (The Canadian Geographer / Le Géographe canadien, 1994)
Keywords: Langue; Quartiers

Un shtetl dans la ville: la zone de résidence juive à Montréal avant 1945 - Anctil, Pierre (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Juifs

''A Letter from the Sabbath Queen'' Rabbi Yudel Rosenberg Addresses Montreal Jewry - Robinson, Ira (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Rosenberg, Yudel

Analyse sociolinguistique de deux discours féministes - Helme, Mireille (Université McGill, 1984)
Keywords: Féminisme; Les Têtes de Pioche (journal)

Institutional completeness, ethnic organizational style and the role of the state: the Jewish, Italian and Greek communities of Montreal - Rosenberg, Michael; Jedwab, Jack (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1992)
Keywords: Grecs; Italiens; Juifs

Beyond Physical Boundaries: The Symbolic Construction of Chinatown - Morrison, Val M. (Université Concordia, 1992)
Keywords: Chinois; Quartier chinois; Quartiers

The Senator, The Merchant, Two Carpenters and a Widow: A Survey of Canadian Landlords in 1871 - Burley, David G. (Urban History Review / Revue d'histoire urbaine, 1997)
Keywords: Logement

The Jackie Robinson Myth: Social Mobility and Race in Montreal, 1920-1960 - Williams, Dorothy W. (Université Concordia, 1999)
Keywords: Enseignants; Lord, Gwen; Lord, Richard; Noirs; Robinson, Jackie

The Refugee Youth Program in Montreal 1947-1952. A Descriptive and Analytical Study of the Integration of 40 Jewish Refugee Youths into the Montreal Community - Fischer, Greta; Switzer, Pearl (Université McGill, 1955)
Keywords: Enfants; Juifs

The Indian Business Community in Montreal from 1967 to 1991 - Meenakshi, Gupta (Université du Québec à Trois-Rivières, 1995)
Keywords: Hommes d'affaires; Indiens

The Contributions of Montreal Holocaust Survivor Organizations to Jewish Communal Life - Giberovitch, Myra (Université McGill, 1988)
Keywords: Juifs

Private Rehabilitation in a Low Rent Area: Landlord-Tenant Relations and other Non-Market Factors - Duff, Huntly Douglas (Université McGill, 1973)
Keywords: Locataires; Logement; Portugais

Entente cordiale? La section montréalaise du Fonds patriotique canadien, 1914-1923: le bénévolat de guerre à Montréal - Morton, Desmond (Revue d'histoire de l'Amérique française, 1999)
Keywords: Bénévolat; Guerre

Immigration et maladies mentales chez les haïtiens de Montréal - Dubuisson, Wilfrid (Université de Montréal, 1979)
Keywords: Haïtiens

Un groupe d'immigrants belges face aux organismes qui s'occupent du bien-être et de l'intégration des immigrants dans la région montréalaise: étude des connaissances et des attitudes des quarante et un immigrants belges à l'égard des organismes qui s'occupent du bien-être et de l'intégration des immigrants, et analyse de l'utilisation faite des services de ces organismes - Dedobbeleer, Nicole (Université de Montréal, 1970)
Keywords: Belges

Sensibilité juive chez trois poètes de Montréal - Scott, Michael (Annales du centre de recherches sur l'Amérique anglophone, 1981)
Keywords: Juifs; Poésie

Les écrivains juifs de Montréal - Anctil, Pierre (Juifs et réalités juives au Québec, 1984)
Keywords: Juifs; Écrivains

From Yiddish to "Yiddishkeit": A. M. Klein, J. I. Segal and Montreal's Yiddish Culture - Fuerstenberg, Adam (Journal of Canadian Studies / Revue d'études canadiennes, 1984)
Keywords: Juifs; Klein, A. M.; Segal, J. I.; Écrivains

Omer Héroux and La Vérité, 1904-1908: French-Canadian Nationalism and Catholicism in the Early Twentieth Century - Morrison, H. Jean (Université Concordia, 1992)
Keywords: Nationalisme; Écrivains

Jews & French Quebecers: Two Hundred Years of Shared History - Langlais, Jacques; Rome, David (Wilfrid Laurier University Press, 1991)
Keywords: Francophones; Juifs

La réception critique de la peinture de Jean Paul Lemieux ou la construction d'une figure identitaire - Couture, Francine (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)
Keywords: Peinture

Notre maître: le passé? Nationalisme et antisémitisme au Devoir, 1932-1947 - Jedwab, Jack (Le Devoir: un journal indépendant, 1910-1995, 1996)
Keywords: Devoir (Le); Juifs; Nationalisme

L'émergence d'une identité québécoise dans la dramaturgie anglo-montréalaise - Hulslander, Kenneth (Université du Québec à Montréal, 1994)
Keywords: Anglophones; Théâtre

Espaces observés: ethnicité et appropriation territoriale - Le Gall, Josiane; Meintel, Deirdre (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Les paramètres épistémologiques et idéologiques d'un premier discours sur la modernité - Trépanier, Esther (Des lieux de mémoire: identité et culture modernes au Québec, 1930-1960, 1995)

Romanticism, Home, and Death: Elements in the Lives of the Anglophone Elite in Early Victorian Montreal - Young, Brian (Australian-Canadian Studies, 1997)
Keywords: Anglophones

Les pierres qui parlent: deux cents ans d'enracinement de la communauté juive au Québec - Langlais, Jacques; Rome, David (Septentrion, 1992)
Keywords: Juifs

La construction médiatique du "Bronx" de Montréal - El Yamani, Myriame; Dupuis, Jocelyne (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Quelques observations sur les mariages irlandais dans la paroisse Notre-Dame de Montréal (1840-1861) - Beaudoin, Philippe (Canadian Ethnic Studies / Études ethniques au Canada, 1998)
Keywords: Irlandais; Mariage; Notre-Dame (paroisse)

Genèse d'une communauté lesbienne: un récit des années 1970 - Hildebran, Andrea (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Anglophones; Femmes; Francophones

Motivation in Hip-Hop Graffiti Culture: The Site of Tension between Individual Desire, Peer Influence and Community Space - Rahn, Janice (Université Concordia, 1999)

Uniting Uptowners and Downtowners: The Jewish Electorate and Quebec Provincial Politics: 1927-39 - Jedwab, Jack (Canadian Ethnic Studies / Études ethniques au Canada, 1986)
Keywords: Juifs; Élections

Geschichte der Deutschen Gesellschaft zu Montreal, 1835-1985 - Gurttler, Karin (Deutche Gesellschaft zu Montreal, 1985)
Keywords: Allemands

La production canadienne-française à l'Office national du film du Canada de 1939 à 1964 - Véronneau, Pierre (Université du Québec à Montréal, 1986)
Keywords: Cinéma; Office national du film

Histoire de la Société Saint-Jean-Baptiste de Montréal: des patriotes au Fleurdelisé, 1834-1948 - Rumilly, Robert (L'Aurore, 1975)
Keywords: Société Saint-Jean-Baptiste

Histoire du Québec anglophone 1759-1980 - Rudin, Ronald (Institut québécois de recherche sur la culture, 1986)
Keywords: Anglophones

The Forgotten Quebecers. A History of English-Speaking Quebec 1759-1980 - Rudin, Ronald (Institut québécois de recherche sur la culture, 1985)
Keywords: Anglophones

A Study of the Changes in the Geographic Distribution of the Jewish Population in Metropolitan Montreal, 1851-1951 - Rosenberg, Louis (Canadian Jewish Congress, 1955)
Keywords: Juifs

Juifs et Québécois français. 200 ans d'histoire commune - Rome, David; Langlais, Jacques (Fides, 1986)
Keywords: Francophones; Juifs

Les premiers Italiens de Montréal: l'origine de la Petite Italie du Québec - Ramirez, Bruno (Boréal Express, 1984)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Conflits d'identité et d'allégeance. La propagande du consulat italien à Montréal dans les années 1930 - Perin, Roberto (Questions de culture, 1982)
Keywords: Italiens

Processions de la Saint-Jean-Baptiste en 1924 et 1925; accompagnés de biographies et portraits des présidents généraux de la Société Saint-Jean-Baptiste de Montréal [...] (1834-1926) - Massicotte, E.-Z. (s.é., 1926)
Keywords: Société Saint-Jean-Baptiste

Les mécanismes privés d'accueil et d'assistance aux immigrants. Une étude de cas: la Société d'assistance aux immigrants, 1950-1957 - Lévesque, Edna (Université du Québec à Montréal, 1991)
Keywords: Société d'assistance aux immigrants

1843-1985, Montreal's Hellenism - Bombas, Léonidas C. (Hellenic Psychological and Pedagogical Institute of Montreal, 1985)
Keywords: Grecs; Étudiants

Les relations ethniques dans la vie politique montréalaise - Bourassa, Guy (Information Canada, 1971)
Keywords: Anglophones; Francophones

Les relations ethniques dans la vie politique montréalaise - Bourassa, Guy (Commission royale d'enquête sur le bilinguisme et le biculturalisme, 1966)
Keywords: Anglophones; Francophones

Les relations ethniques dans la vie politique montréalaise - Bourassa, Guy (Le système politique de Montréal, 1986)
Keywords: Anglophones; Francophones

La tunique aux couleurs multiples. Deux siècles de présence juive au Canada - Abella, Irving (Musée canadien des Civilisations, 1990)
Keywords: Juifs

A Coat of Many Colours. Two Centuries of Jewish Life in Canada - Abella, Irving (Lester and Orpen Dennys, 1990)
Keywords: Juifs

Montreal Chinese Property Ownership and Occupational Change, 1881-1981 - Aiken, Rebecca Bruff (Université McGill, 1985)
Keywords: Chinois; Travail

Progrès, harmonie, liberté: le libéralisme des milieux d'affaires francophones de Montréal au tournant du siècle - Roy, Fernande (Boréal, 1988)
Keywords: Idéologies; Libéralisme

Les Anglophones du Québec de majoritaires à minoritaires - Caldwell, Gary; Waddell, Eric (Institut québécois de recherche sur la culture, 1982)
Keywords: Anglophones

Introduction to the Social History of the Scots in Quebec (1780-1840) - Price, Lynda (National Museums of Canada, 1981)
Keywords: Histoire; Écossais

Notes sur les relations entre les hospitalières de Montréal et les Irlandais - Kerr, Corinne (L'Hôtel-Dieu de Montréal, 1973)
Keywords: Communautés religieuses; Hospitalières de Saint-Joseph; Hôtel-Dieu; Irlandais

Origines, richesse et travail / Origins, Wealth and Work - Fyson, Donald; Young, Brian (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: Irlandais; McCord (famille)

Les esclaves aux 17e et 18e siècles - Lachance, André (Les marginaux, les exclus et l'autre au Canada aux XVIIe et XVIIIe siècles, 1996)
Keywords: Autochtones; Esclaves; Noirs

L'œuvre des réfugiés hongrois et l'adaptation à Montréal d'un groupe de réfugiés hongrois: une étude de l'influence de l'ORH sur l'adaptation, au niveau de leurs besoins élémentaires, d'un groupe de réfugiés hongrois arrivés à Montréal entre le quinze décembre 1956 et le quinze juillet 1957 et ayant reçu des services de cette agence - Corbeil, Yvan; Laurent-Boyer, Lise; Richard, Mireille (Université de Montréal, 1960)
Keywords: Hongrois

A Study of the Academic Achievement and Personal and Social Adjustment of Jewish Moroccan Immigrant Students in the English High Schools of Montreal - Godfrey, Marvin Julian (Université McGill, 1970)
Keywords: Juifs; Maghrébins; Marocains

Quartier ethnique et propriété foncière: le cas de la communauté italienne de Montréal - Laplace, Gérard (Université de Montréal, 1984)
Keywords: Italiens; Logement; Quartiers

Comportement économique des "propriétaires" et "locataires" d'origine canadienne et étrangère dans un secteur résidentiel éloigné du centre-ville de Montréal - Dugas, Gilles (Université de Montréal, 1982)
Keywords: Locataires

La ségrégation résidentielle ethnique à Montréal - Lapointe, Alain (Université des sciences sociales de Toulouse, 1978)

Rononshonni - le Bâtisseur. La collection McCord d'objets ethnographiques - McCaffrey, Moira T. (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: McCord, David Ross; Musée McCord; Musées

La fête du Santo Cristo à Montréal: histoire, idéologie et mentalité du peuple portugais - Araujo, Antonio (Université de Montréal, 1991)
Keywords: Portugais

Minorisation politique des francophones au Québec: les élections provinciales dans la région métropolitaine de Montréal (1966-1985) - Pelletier, Alain (Université de Montréal, 1988)
Keywords: Francophones; Élections

The Political Behavior of Two Montreal Anglophone Constituencies during the Duplessis Era, 1935-1956: The Case of Westmount and Notre-Dame-de-Grâce - Jedwab, Jack (Université Concordia, 1982)
Keywords: Anglophones; Notre-Dame-de-Grâce; Quartiers; Westmount

Gender and Division of Labour in a Vietnamese-Canadian Buddhist Pagoda - Soucy, Alexander (Université Concordia, 1994)
Keywords: Femmes; Travail; Vietnamiens

"La Sosta dello Spirito": autocritique - relance d'une rubrique de caractère religieux et en langue italienne au poste de radio C.F.M.B. 1410 à Montréal - Giuseppe, Castelli (Université de Montréal, 1975)
Keywords: Italiens; Radio

Writing Bodies: Modern Dance, Gender, and Jewish Identity in New York and Montreal, 1930 to 1960 - Hardt, Yvonne (Université Concordia, 1999)
Keywords: Danse; Juifs

Le comportement électoral des minorités au Québec lors des élections de 1976 - Jedwab, Jack (Bulletin de l'association québécoise d'histoire politique, 1994)
Keywords: Anglophones; Élections

L'opinion publique anglo-québécoise et l'autonomie provinciale (1945-1946) - Trépanier, Pierre (L'Action nationale, 1977)
Keywords: Montreal Gazette; Montreal Star

The Contours of Canadian Jewish History - Tulchinsky, Gerald (Journal of Canadian Studies / Revue d'études canadiennes, 1982)
Keywords: Juifs

Jackie Robinson: une inoubliable saison de baseball à Montréal - Jedwab, Jack (Les Éditions Images, 1997)
Keywords: Baseball; Robinson, Jackie

The Journal of Yaacov Zipper 1925-1926 - Garfinkle, Ode; Butovsky, Mervin (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs

Le libéralisme au Québec: l'idéologie des milieux d'affaires francophones à Montréal, 1881-1914 - Roy, Fernande (Université du Québec à Montréal, 1986)
Keywords: Idéologies; Libéralisme

H.-M. Caiserman: Yiddish as a Passion - Anctil, Pierre (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs

Public Lives in Private: Ida Maze and the Montreal Yiddish Renaissance - Massey, Irving (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Poésie

Between Two Worlds: The Works of J.-I. Segal - Cooper Friedman, Shari (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Poésie; Segal, J. I.

La reconquête de Montréal - Levine, Marc V. (Études Québécoises, 1997)
Keywords: Anglophones; Francophones

Ethnic Political Participation in Montreal: the Role of Community Leaders - Lapp, Miriam (Université de Montréal, 1997)
Keywords: Chinois; Grecs; Italiens; Juifs; Portugais; Élections

Jewish Supplementary Schooling in Montreal in the Latter Part of the Twentieth Century - Segal, Sima (Université McGill, 1991)
Keywords: Bureau des écoles protestantes; Juifs; Langue

Family, Paesani and Networks: Politics and Economy of Montreal Italians - Aramaki, Michiko (Université McGill, 1994)
Keywords: Italiens

Antisémitisme et nationalisme d'extrême-droite dans la province de Québec 1929-1939 - Delisle, Esther (Université Laval, 1992)
Keywords: Devoir (Le); Groulx, Lionel; Juifs; Nationalisme

West Indian Associations in Montreal - Handelman, Don (Université McGill, 1964)
Keywords: Caribéens; Clubs

L'Action française: l'appel à la race - Robertson, Susan Mann (Université Laval, 1970)
Keywords: Action française (L'); Nationalisme

Action française: French Canadian Nationalism in the Twenties - Trofimenkoff, Susan Mann (University of Toronto Press, 1976)
Keywords: Action française (L'); Nationalisme

Le Devoir, les Juifs et l'immigration. De Bourassa à Laurendeau - Anctil, Pierre (Institut québécois de recherche sur la culture, 1988)
Keywords: Bourassa, Henri; Devoir (Le); Juifs; Laurendeau, André

La littérature montréalaise et les ghettos - Melançon, Benoît (Voix et Images, 1991)
Keywords: Quartiers; Écrivains

Le processus identitaire dans le soccer chez les italiens de Montréal - Spadari, Luigi (Université de Montréal, 1998)
Keywords: Italiens; Soccer

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

Les descendants d'Hochelaga: étude de la représentation autochtone à travers le toponyme Hochelaga et les productions artistiques et commerciales du Vieux-Montréal - Doiron, Roger (Université du Québec à Montréal, 1998)
Keywords: Autochtones; Quartiers; Vieux-Montréal

Un royaume en exil: le judaïsme montréalais - Anctil, Pierre (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Juifs

Vivre un choc culturel à 65 ans: le cas des personnes âgées haïtiennes en HLM à Montréal - Bontemps, Eva (Université du Québec à Montréal, 1997)
Keywords: Haïtiens; Logement

Cloisonnement ethnique et solidarité captive. Famille Lao dans le quartier Côte-des-Neiges - Bertheleu, Hélène; Billion, Pierre (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Laotiens; Quartiers

Différenciation sociale et rituels du mariage: les Montréalais francophones, 1925-1940 - Girard, Denise (Université Laval, 1998)
Keywords: Francophones; Mariage

Le phénomène des jeunes de la rue à Montréal le cas des Haïtiens - Uwumuremyi, Marie D'Amour (Université du Québec à Montréal, 1998)
Keywords: Haïtiens; Itinérance

Représentation et rôle des Québécois / Canadiens français dans le radioroman de guerre 1939-1945 - Legris, Renée (Bulletin d'histoire politique, 1995)
Keywords: Guerre; Radio; Roman

Minorités, majorités et les territoires du quotidien - Ulysse, Pierre Joseph; McAll, Christopher (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

La colocation comme situation de communication interculturelle, le discours de cinq jeunes français vivant avec des québécois - Ferrand, Nathalie (Université du Québec à Montréal, 1999)
Keywords: Français; Locataires; Logement

Structure familiale et pouvoir conjugal dans des familles haïtiennes de Montréal - Lasry, Jean-Claude; Frédérik, Mario (Canadian Ethnic Studies / Études ethniques au Canada, 1986)
Keywords: Famille; Haïtiens

Montreal E Il Suo Certificato Di Nascita, 1535-1985: Ommagio Alla Nostra Citta Nel Suo 450mo Anno Di Nascita/Montréal et son certificat de naissance, 1535-1985: à notre ville à l'occasion de son 450ième anniversaire de naissance - Menchini, Camillo M. (C. Menchini, 1985)
Keywords: Cartier, Jacques; Hochelaga; Italiens

The traitor and the Jew: Anti-Semitism and Extremist Right-Wing Nationalism in Quebec from 1929 to 1939 - Delisle, Esther (Food for thought, 1993)
Keywords: Idéologies; Juifs; Nationalisme

The Segregated City: Class Residential Patterns and the Development of Industrial Districts in Montreal 1861 and 1901 - Lewis, Robert D. (Journal of Urban History, 1991)
Keywords: Locataires; Logement; Mobilité résidentielle

Étude sur le rôle de l'Église dans l'intégration des immigrés d'origine italienne dans la société montréalaise - Castelli, Giuseppe (Université de Montréal, 1980)
Keywords: Italiens; Églises

Fréquentations, mariage et divorce chez les Salvadoriens de Montréal - Juteau, Francine (Université de Montréal, 1989)
Keywords: Mariage; Salvadoriens

A Political Analysis of School Reorganization in Montreal - Fournier, Pierre (Université McGill, 1971)

Secular and Parochial Education of Ashkenazi and Sephardi Jewish Children in Montreal: A Study in Ethnicity - Hirschberg, Jack Jacob (Université McGill, 1988)
Keywords: Enfants; Juifs

Italian Influences on the Cultural Life of Old Montreal - Goggio, Emilio (Canadian Modern Language Review, 1952)
Keywords: Italiens; Quartiers; Vieux-Montréal

Montréal en images: exotisme et triomphalisme (1855-1914) - Lessard, Michel (Cap-aux-Diamants, 1991)
Keywords: Anglophones; Britanniques; Photographie

Le traître et le juif: Lionel Groulx, Le Devoir, et le délire du nationalisme d'extrême droite dans la province de Québec: 1929-1939 - Delisle, Esther (Pluralisme, 1992)
Keywords: Devoir (Le); Groulx, Lionel; Juifs; Nationalisme

City Unique: Montreal days and nights in the 1940s and '50s - Weintraub, William (McClelland & Stewart, 1996)

Une poésie de dissidence: étude comparative de l'évolution des poésies québécoise et canadienne modernes à Montréal, 1925-1955 - Giguère, Richard (Université de Colombie-Britannique, 1978)
Keywords: Poésie

Le Rapical montréalais, étude de phonétique expérimentale - Cossette, André (Université Laval, 1969)

Le Père Émile Legault: l'homme et l'oeuvre - Lindsay-Keay, Anne Caron (University of British Columbia, 1974)
Keywords: Compagnons de Saint-Laurent; Legault, Émile; Théâtre

La mobilité résidentielle au centre de l'île de Montréal: essai de géographie sociale - Awada, Atef (Université de Montréal, 1988)
Keywords: Mobilité résidentielle

Arab Immigrants in the Canadian Labour Market Expectations and Compromises - Al-Hihi, Mahmoud M (Université Concordia, 1997)
Keywords: Arabes; Travail

Les immigrants français à Montréal, 1850-1901. Étude des Français présents à Montréal lors du recensement de 1901 - Filot, Ingrid (Université Lumière Lyon 2, 1995)
Keywords: Français

Répartition sectorielle et occupationnelle des travailleurs haïtiens sur le marché du travail à Montréal - Vernet, Pericles Jean (Université du Québec à Montréal, 1987)
Keywords: Haïtiens; Travail

Essai de définition: les sculpteurs, statuaires et ornemanistes italiens à Montréal: de 1862 à 1880 - Vignola, Luce (Université du Québec à Montréal, 1996)
Keywords: Artisans; Italiens; Sculpture

Immigration et marché du travail: les ouvriers polonais à Montréal, 1926-1944 - Gwiazda, Wojtek (Cahiers d'histoire, 1985)
Keywords: Polonais; Travail

Les travailleurs juifs de la confection à Montréal (1910-80) - Rouillard, Jacques (Labour / Le travailleur, 1981)
Keywords: Confection; Juifs; Vêtements

The Poalei Zion Movement in Canada 1904-1920 (texte en Yiddish) - Belkin, S. (Labour Zionist Movement, 1956)
Keywords: Juifs; Poalei Zion (Mouvement sioniste ouvrier)

Workers Without a Cause: Italian Immigrant Labour in Montreal, 1880-1930 - Ramirez, Bruno (Arrangiarsi. The Italian Immigration Experience in Canada, 1989)
Keywords: Italiens; Travail

Cent vingt-cinq ans d'oeuvres sociales et économiques: réhabilitation historique - Morin, Victor (Éditions des Dix, 1959)
Keywords: Société Saint-Jean-Baptiste

Job Satisfaction and Job Stress as Related to Intergenerational Occupational Mobility, Vertical Job Mobility, Horizontal Job Mobility and Job Mobility Orientation: A Study of the Greek-Canadians of Montreal - Sarmaniotis, Christos (Université Concordia, 1980)
Keywords: Grecs; Travail

La condition des domestiques antillaises à Montréal - Bled, Yves (Université de Montréal, 1965)
Keywords: Caribéens; Domestiques

La pratique de la musique liturgique et paraliturgique des Juifs originaires du Maroc à Montréal - Sabbah, Dina (Université de Montréal, 1989)
Keywords: Juifs; Maghrébins; Marocains; Musique

Canadiens français et non-francophones dans les villes québécoises et ontariennes, 1851-1911: une perspective comparative et régionale - Ouellet, Fernand (La francophonie ontarienne: bilan et perspectives de recherche, 1995)
Keywords: Francophones

Les buandiers chinois de Montréal au tournant du siècle - Helly, Denise (Recherches sociographiques, 1984)
Keywords: Chinois

Brief Encounters: Italian Immigrant Workers and the CPR, 1900-30 - Ramirez, Bruno (Labour / Le travailleur, 1986)
Keywords: Canadien Pacifique; Italiens

«C'est l'eau-de-vie qui a commis ce meurtre». Alcool et criminalité amérindienne à Montréal sous le Régime français - Dickinson, John A. (Études canadiennes / Canadian Studies, 1993)
Keywords: Alcool; Autochtones; Criminalité

Montreal Jewry in the Era of the de Solas - Tulchinsky, Gerald J. J. (Taking Root: The Origins of the Canadian Jewish Community, 1993)
Keywords: De Sola, Abraham; Juifs

Le chômage des jeunes de la communauté haïtienne de Montréal: les diplômés-es de l'UQAM - Pognon, Renel (Université du Québec à Montréal, 1992)
Keywords: Chômage; Haïtiens; Travail; Université du Québec à Montréal

Le «boom» des immeubles d’appartements à Montréal de 1921-1951 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1994)
Keywords: Logement; Outremont; Westmount

La société canadienne-française et le théâtre lyrique à Montréal entre 1840 et 1913 - Barrière, Mireille (UMI Dissertation Services, 1991)
Keywords: Francophones; Théâtre

Les communautés protestantes francophones au Québec, 1834-1925 - Vogt-Raguy, Dominique (Université Michel de Montaigne-Bordeaux 3, 1996)
Keywords: Francophones; Protestants

Le sport chez les Canadiens-français de Montréal au XIXe siècle - Janson, Gilles (Université du Québec à Montréal, 1993)
Keywords: Baseball; Crosse; Football; Palestre nationale; Raquetteurs

Becoming Native in a Foreign Land: Visual Culture, Sport, and Spectacle in the Construction of National Identity in Montreal, 1840-1885 - Poulter, Gillian (York University, 1999)
Keywords: Autochtones; Britanniques; Français

Emparons-nous du sport: les Canadiens français et le sport au XIXe siècle - Janson, Gilles (Guérin, 1995)
Keywords: Francophones

Une nouvelle association professionnelle: le Publicité-Club: étude monographique de la professionnalisation du publicitaire canadien-français à Montréal, dans le contexte du développement de cette industrie au Canada - Lacroix, Lucien (Université de Montréal, 1967)
Keywords: Publicité

La société canadienne-française et le théâtre lyrique à Montréal entre 1840 et 1913 - Barrière, Mireille (Université Laval, 1990)
Keywords: Francophones; Théâtre

The English Speaking Catholic People of Montreal - Litalien, Rolland (L'Église de Montréal, aperçus d'hier et d'aujourd'hui, 1836-1986, 1986)
Keywords: Anglophones

The Road to Now: A History of Blacks in Montreal - Williams, Dorothy W. (Dossier Québec, 1997)
Keywords: Noirs

Ethnicity and Home Ownership in Montreal, 1921–51 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1998)
Keywords: Locataires; Logement

Antiracism organizing and resistance in nursing : African Canadian Women - Calliste, Agnes (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1996)
Keywords: Africains; Femmes; Infirmières; Noirs

Le monument inattendu, le Monument-National, 1893-1993 - Larrue, Jean-Marc (Cahiers du Québec - Collection Histoire, 1993)
Keywords: Société Saint-Jean-Baptiste; Théâtre; École nationale de théâtre du Canada

ONASAKENRAT, JOSEPH - Smith, Donald B. (Dictionnaire biographique du Canada, 1982)

Relations entre mobilité socio-professionnelle et intégration des immigrants: les Grecs de Montréal - Brédimas-Assimopoulos, Constantina (Université de Montréal, 1975)
Keywords: Grecs

The Economic Adjustment of North African Jewish Immigrants in Montreal - Moldofsky, Naomi (Université McGill, 1968)
Keywords: Juifs; Maghrébins

Trabajo Asalariado, género e identidad: la inserción de las Mujeres Colombianas en Montreal - Osorio Ramírez, Amantina Maria (Université de Montréal, 1996)
Keywords: Colombiens; Femmes; Travail

Immigration and Charity in the Montreal Jewish Community before 1890 - Tulchinsky, Gerald (Histoire sociale / Social History, 1983)
Keywords: Juifs; Philanthropie; Young Men's Hebrew Benevolent Society

Immigration, Ethnicity, and the Labour Market: The Chinese in Montreal - Pao-Mercier, Laura Yrien-Ha (Université McGill, 1982)
Keywords: Chinois; Travail

Le monde du travail comme moyen d'intégration des Portugais au Québec (1953-1995): ou comment marier le vieux et le neuf - Lopes, Duarte (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1995)
Keywords: Portugais

Les Irlandais catholiques de Montréal: introduction historique et méthodologique - Slattery, Maureen (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Irlandais

Histoire et histoires dans la métropole québécoise: le quartier Côte-des-Neiges - Ramirez, Bruno (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Le raz de marée irlandais à Montréal - Olson, Sherry; Thornton, Patricia (Les chemins de la migration en Belgique et au Québec: XVIIe-XXe siècles, 1995)
Keywords: Irlandais

Blacks in Montreal, 1628-1986: An Urban Demography - Williams, Dorothy W. (Éditions Yvon Blais, 1989)
Keywords: Noirs

An Analysis of the Payrolls of the Point St. Charles Shops of the Grand Trunk Railway - Hoskins, Ralph F. H. (Cahiers de géographie du Québec, 1989)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

Ethnicity and Housing Adaptation: the Italians in Montreal - Fainella, John G. (Université McGill, 1986)
Keywords: Italiens; Logement

Montreal of Yesterday: A Snapshot of Jewish Life in Montreal During the Era of Mass Immigration - M. Baker, Zachary (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Medres, Israel Jonah

Shadrach Minkins: From Fugitive Slave to Citizen - Collison, Gary (Harvard University Press, 1998)
Keywords: Esclaves; Noirs

Le peuplement de Montréal - Olson, Sherry (Atlas historique du Québec. Population et territoire, 1996)

Église St. Patrick - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Irlandais; Patrimoine; Saint-Patrick (église)

Jewish labour and business in the dressmakers'strikes of tje 1930: A clash of cultures in a confined space - Tulchinsky, Gerald (Espace et culture, 1995)
Keywords: Grèves; Juifs; Vêtements

L'entrepreneurship à Côte-des-Neiges: le périmètre Victoria / Van Horne - Juteau, Danielle; Paré, Sylvie (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Smoke and Fire: The Chinese in Montreal - Kwok Bun, Chan (The Chinese University Press, 1991)
Keywords: Chinois

The Politics of the Société Saint-Jean-Baptiste de Montréal - Agen, Marie-Catherine (American Review of Canadian Studies, 1999)
Keywords: Francophones; Nationalisme; Société Saint-Jean-Baptiste

Struggling on Many Fronts: Gender, Work and Unionization - Aguiar, Luis (McMaster University, 1991)
Keywords: Textile; Vêtements

Familles montréalaises du XIXe siècle: trois cultures, trois trajectoires - Olson, Sherry; Thornton, Patricia (Cahiers québécois de démographie, 1992)
Keywords: Anglophones; Famille; Irlandais

Par monts et par vaux. Migrants canadiens-français et italiens dans l’économie nord-atlantique, 1860-1914 - Ramirez, Bruno (Boréal, 1991)
Keywords: Italiens; Travail

On the Move: French-Canadian and Italian Migrants in the North Atlantic Economy, 1860-1914 - Ramirez, Bruno (The Canadian Social History Series, 1991)
Keywords: Italiens; Travail